3D microcrystalline glass as well as preparation method and application thereof

By using partially crystallized microcrystalline glass for thermal bending and crystallization during 3D thermal bending, the problems of high mechanical processing difficulty and reduced optical performance in 3D thermal bending are solved, and higher dimensional accuracy and optical performance are achieved, reducing production costs.

CN119874201APending Publication Date: 2025-04-25CHONGQING AUREAVIA HI TECH GLASS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411812731.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-01-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing fully crystallized microcrystalline glass has high mechanical strength and hardness during the 3D thermal bending process, but it leads to low mechanical processing yield and high production cost. The thermal bending molding temperature must be higher than 700℃, resulting in crystal phase changes that greatly affect the display effect and imaging quality.

Method used

Partially crystallized microcrystalline glass is used for 3D thermal bending, and crystallization is carried out while the thermal bending deformation is carried out to achieve the target crystallinity, reduce the crystallization process and improve the dimensional accuracy.

Benefits of technology

It improves the dimensional accuracy and optical performance of 3D microcrystalline glass, reduces production costs and energy consumption, avoids the problem of repeated crystallization, and improves the yield rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874201A_ABST
    Figure CN119874201A_ABST
Patent Text Reader

Abstract

The invention provides a 3D microcrystalline glass, which is characterized in that the crystallinity of the 3D microcrystalline glass is 14-100 wt%; the average particle size of the crystals of the 3D microcrystalline glass is 10 to 100 nm; the thickness of the 3D microcrystalline glass ranges from 0.02 mm to 5 mm. The preparation method of the 3D microcrystalline glass is small in processing difficulty and low in processing cost, and the 3D hot bending crystallization time is far shorter than the conventional crystallization time; the time cost is saved, and meanwhile heat treatment energy is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass preparation technology, and specifically to a 3D microcrystalline glass and its preparation method and application. This invention patent application is a divisional application of the invention patent application with application number 202110099277.4, application date January 25, 2021, and invention name “A 3D microcrystalline glass and its preparation method and application”. Background Art

[0002] As a new generation of high-strength glass, microcrystalline glass has higher performance than traditional lithium aluminum silicon glass. Because microcrystalline glass contains a large number of nano-scale crystals, it has a more stable structure and can obtain a higher strength cover product after chemical strengthening.

[0003] The 3D hot bending process of the mobile phone cover requires the following equipment and raw materials: 3D hot bending machine, 3D hot bending mold (usually graphite mold) and glass raw materials. The processing technology of 3D hot bending mobile phone cover glass is generally carried out through the following steps: first, the glass plate is formed by float, calendering and overflow, then through cutting and thinning steps, and then CNC processing, polishing, 3D hot bending, 3D polishing and chemical strengthening. 3D hot bending is carried out using a hot bending machine, which includes preheating, forming and cooling stations. The preheating station includes a preheating mold and a glass sheet. Its function is to promote the uniformity of the temperature inside and outside the glass. The cooling station uses cooling water to quickly cool the mold so that the glass temperature gradually decreases from the forming temperature to the demolding temperature. The 3D hot bending mold is a graphite mold, which is divided into two parts, the upper and lower parts. After the glass sheet is placed in the mold, it goes through the preheating, forming and cooling stations to complete the entire 3D hot bending process. In order to ensure the output efficiency of the 3D hot bending process, there are requirements for the length of time for each station. In the specific operation, the processed and cleaned glass piece is placed in the 3D mold, and then the mold is placed in the 3D hot bending machine for 3D hot bending according to the preset process.

[0004] The principle used in the 3D hot bending process is that after glass or glass ceramics are heated to a temperature near the softening point, they can change shape under the action of external force, and then quickly cool down after the shape change, so that the shape obtained after hot pressing can be maintained. The preheating step in the 3D hot bending process can prevent the glass from being cracked due to heat at high temperatures during molding. The molding temperature is above the softening point, and the glass softens quickly. At the same time, the upper and lower surfaces of the mold are pressurized by the pressure rod to bend the glass plate into shape, and the pressure is maintained before cooling to maintain the shape of the glass plate. The mold is then quickly cooled by cooling water. In addition, the 3D hot bending process is protected by nitrogen throughout to prevent mold oxidation.

[0005] After forming, cutting and thinning, the glass plate is processed by CNC to reduce defects such as cracks on the edges, and polished to give the upper and lower surfaces of the glass plate a polished effect. 3D hot bending of the CNC and polished glass plate can reduce the breakage rate of the glass plate during the hot bending process. Summary of the invention

[0006] The existing 3D hot-bent glass-ceramics are formed by hot-bending completely crystallized glass-ceramics, and the processing procedures include glass plate forming, glass plate nucleation and crystallization, crystallized glass plate thinning, crystallized glass plate cutting, CNC, polishing, and 3D hot bending, 3D polishing and chemical strengthening are performed only after it is completely crystallized. The existing completely crystallized glass-ceramics have higher mechanical strength and hardness, resulting in low mechanical processing yield and high production cost of the existing completely crystallized glass-ceramics before hot bending.

[0007] The softening molding temperature of existing fully crystallized microcrystalline glass is generally above 700℃, so the 3D hot bending molding temperature must be higher than 700℃. During the hot bending process, the fully crystallized microcrystalline glass will be heated, and its original crystal phase type, crystal size, refractive index, Lab (chromaticity) value, haze, transmittance, etc. will change greatly. Applied in display scenarios, the chromaticity and transmittance of microcrystalline glass will directly affect the display effects such as display resolution, color gamut, and saturation; applied to camera objective lenses, the refractive index, haze, and transmittance of microcrystalline glass, especially the ultraviolet and near-ultraviolet transmittance, have an important impact on the optical system of photography and videography. When the ultraviolet and near-ultraviolet transmittance is low, it will directly affect the imaging quality.

[0008] In addition, the existing 3D hot bending of fully crystallized microcrystalline glass is only for the purpose of hot bending, and there is repeated crystallization, resulting in a waste of energy and time. Therefore, the existing 3D hot bending of fully crystallized microcrystalline glass has extremely high technical difficulty, and it is difficult to achieve the yield required by industrial production by using its 3D hot bending to process into a 3D shape.

[0009] However, if we do not use fully crystallized microcrystalline glass for 3D hot bending, but use nucleated glass for 3D hot bending, because in the early stage of hot bending crystallization of nucleated glass, the volume shrinkage caused by the crystals grown on the interface between the crystal nucleus and the glass is very obvious, the more the proportion of crystals grows, the greater the volume change of the product, and the size control is very difficult. Therefore, the nucleated glass will undergo a relatively large volume change during the hot bending crystallization process, affecting the dimensional accuracy of the 3D hot bent microcrystalline glass after forming.

[0010] Therefore, the present invention has found that by using partially crystallized microcrystalline glass for 3D hot bending, the glass continues to crystallize when heated while being deformed to reach the target crystallinity, thereby reducing the crystallization process during 3D hot bending, and the dimensional accuracy of the 3D microcrystalline glass after hot bending is higher.

[0011] In addition, in the prior art, a relatively short hot pressing time is controlled during hot bending, because a long hot pressing time will cause mold marks to appear on the surface of the microcrystalline glass product, resulting in reduced surface quality and affecting the yield rate. The method of the present invention uses a partially crystallized glass original sheet for 3D hot bending. The partially crystallized glass original sheet has a high initial crystallinity and is not prone to mold marks. Also, due to the high initial crystallinity of the partially crystallized glass original sheet, the dimensional deformation per unit time is small during the hot pressing process, so it can adapt to a longer hot pressing time, and can more accurately control the deformation after 3D, so that the tolerance fluctuation of the contour degree is small and the size is more stable.

[0012] In order to solve the above technical problems, the present invention aims to provide a 3D microcrystalline glass, characterized in that the crystallinity of the 3D microcrystalline glass is 14-100wt%; and the average particle size of the crystals of the 3D microcrystalline glass is 10-100nm.

[0013] Preferably, the crystallinity of the 3D glass-ceramics is 14-30wt%, or the crystallinity of the 3D glass-ceramics is 50-100wt%; or the crystallinity of the 3D glass-ceramics is 31-49wt%;

[0014] Alternatively, the average particle size of the crystals of the 3D glass-ceramics is 15-30 nm;

[0015] Alternatively, the thickness of the 3D glass-ceramics is 0.02-5 mm, and preferably, the thickness of the 3D glass-ceramics is 0.35-1.2 mm.

[0016] Preferably, the average transmittance of the 3D glass-ceramics at a wavelength of 380-780 nm is 88-93%, preferably 90-91.5%;

[0017] Alternatively, the average transmittance of the 3D glass-ceramics at a wavelength of 360-400 nm is 65-91.5%, preferably 79-91%, and more preferably 85-91%.

[0018] Preferably, the absolute value of the b value (yellow-blue value) of the 3D glass-ceramics when the thickness is 0.7 mm is 0.1-3.5, preferably 0.3-1.5;

[0019] Alternatively, the haze of the 3D glass-ceramics is 0.07-1.0%, preferably 0.07-0.5%.

[0020] Preferably, the crystalline phase of the 3D microcrystalline glass is one or more of lithium silicate, lithium disilicate, β-quartz, β-quartz solid solution, petalite, β-spodumene, β-spodumene solid solution, nepheline, cordierite, mullite, apatite, zirconium dioxide, gahnite, magnesia-aluminum spinel and rutile.

[0021] Preferably, the 3D glass-ceramics contains the following proportions of oxides in mol%:

[0022]

[0023] Wherein, the rare earth oxide is selected from La2O 3 ,Eu 2 O 3 , Pr 6 O 11 , Nd 2 O 3 , Er 2 O 3 and Dy 2 O 3 One or more of the following.

[0024] Preferably, the 3D glass-ceramics contains SiO in mol%. 2 and Al 2 O 3 The total amount is greater than 60%; preferably 68-80%;

[0025] Alternatively, containing Na 2 O+Li 2 The content of O is 7% to 30% by mol%, preferably 10% to 26%.

[0026] Preferably, the 3D glass-ceramics includes a nucleating agent, which is calculated as oxide, fluoride or single substance, and the nucleating agent includes P 2 O 5 , TiO 2 , ZrO 2 ,Cr 2 O 3 , CaF 2 , LiF, NaF, KF, Y 2 O 3 , Au, Ag and Cu, one or more thereof; preferably P 2 O 5 , TiO 2 and ZrO 2 One or more of the following.

[0027] Preferably, the 3D glass-ceramics includes a clarifier, and the clarifier includes NaCl, Na 2 SO 4 , SnO 2 , As 2 O 3 , Sb 2 O 3 , NaNO 3 , KNO3 , CeO 2 and (NH 4 ) 2 SO 4 One or more of; preferably NaCl, SnO 2 , NaNO 3 and CeO 2 One or more of the following.

[0028] Preferably, the crystallized glass original sheet of the 3D microcrystalline glass is a glass sheet having crystals with an average particle size of 5-50 nm after nucleation and crystallization treatment.

[0029] Preferably, the crystallized glass original sheet of the 3D glass-ceramics is a glass sheet having a crystallinity of 5-90 wt % after nucleation and crystallization treatment.

[0030] Preferably, the drop height of the 3D glass-ceramics after chemical strengthening is greater than 1.5 m, and preferably, the Vickers hardness is greater than 650 under a force load of 300 N for 10 s.

[0031] The present invention also provides a method for preparing the above-mentioned 3D glass-ceramics, wherein the preparation method comprises the following steps:

[0032] Step 1: Mix the raw materials for preparing 3D glass-ceramics, melt them, cool them, and perform annealing to obtain a glass substrate;

[0033] Step 2: performing a nucleation treatment on the glass substrate obtained in step 1; wherein the glass substrate may be cut as required before or after the nucleation treatment;

[0034] Step 3: crystallizing the glass substrate after nucleation in step 2;

[0035] Step 4: Cutting the crystallized glass substrate as needed to obtain crystallized glass raw material;

[0036] Step 5: Perform 3D heat bending on the crystallized glass raw material to obtain a 3D micro-ceramic glass sample;

[0037] The 3D hot bending process in step 5 is also accompanied by a crystallization process.

[0038] Preferably, the method may further include the step of subjecting the 3D glass-ceramics sample to chemical strengthening treatment to obtain a 3D glass-ceramics finished product.

[0039] Preferably, in step 1, the melting temperature is 1350-1700°C; preferably, the melting temperature is 1400-1650°C; more preferably, the temperature is cooled to 500-1000°C after melting.

[0040] Preferably, in the step 1, the melting time is 1-5 hours; preferably, in the step 3, crystallization treatment is performed after keeping warm at 500-900°C for 5-300 minutes; further preferably, in the step 3, one or more of trimming, CNC machine tool processing, rough grinding and / or polishing treatments are also included to obtain the crystallized glass raw material.

[0041] Preferably, the amount of the nucleating agent added in step 1 is 1-9 mol% of the total amount of the nucleating agent and the microcrystalline glass oxide, and more preferably the amount of the nucleating agent is 2-5 mol%.

[0042] Preferably, the amount of the clarifier added in step 1 is 0-4 wt %, preferably 0.1-2 wt %, of the total mass of the nucleating agent and the glass-ceramic oxide.

[0043] Preferably, in step 2, the temperature of the nucleation treatment is 450-800°C, and the time of the nucleation treatment is 30-360 minutes; further preferably, the temperature of the nucleation treatment is 520-570°C, and the time of the nucleation treatment is 120-300 minutes.

[0044] Preferably, in step 3, the temperature of the crystallization treatment is 550-900° C., and the time of the crystallization treatment is 5-300 min;

[0045] Preferably, the crystallization temperature is 600-850°C, and the crystallization time is 10-240 minutes.

[0046] More preferably, the temperature of the crystallization treatment is 600-750° C., and the time of the crystallization treatment is 10-150 min.

[0047] Preferably, the hot bending process in step 5 includes a preheating station, a hot pressing station and a cooling station.

[0048] Preferably, the number of the preheating stations is 1-30, preferably 2-4; the number of the hot pressing stations is 1-30, preferably 1-3; the number of the cooling stations is 1-30, preferably 2-4.

[0049] Preferably, the temperature of the preheating station is 300-850°C; the temperature of the hot pressing station is 600-920°C and the pressure is 0-6MPa; the temperature of the cooling station is 200-650°C.

[0050] Preferably, the working time of the preheating station is 20-800 seconds; the working time of the hot pressing station is 20-800 seconds; and the working time of the cooling station is 20-800 seconds;

[0051] Preferably, the working time of the preheating station is 60-600 seconds; the working time of the hot pressing station is 60-480 seconds, and the working time of the cooling station is 60-600 seconds.

[0052] The present invention also provides 3D microcrystalline glass prepared by the preparation method.

[0053] Preferably, the 3D glass-ceramics is characterized in that the 3D glass-ceramics is transparent or opaque; preferably, the 3D glass-ceramics is curved or flat.

[0054] The present invention also provides the use of the above-mentioned 3D microcrystalline glass or the 3D microcrystalline glass described in claim 24 or 25 in mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

[0055] Beneficial effects of the present invention:

[0056] 1. The present invention uses partially crystallized microcrystalline glass for 3D hot bending. While the glass is deformed during hot bending, it continues to crystallize when heated to reach the target crystallinity, reducing the crystallization process during 3D hot bending. The 3D microcrystalline glass after hot bending has higher dimensional accuracy. The preparation method of the 3D microcrystalline glass of the present invention has low processing difficulty and low processing cost, saving time cost and energy for heat treatment. The use of partially crystallized microcrystalline glass for 3D hot bending avoids the problem of repeated crystallization during 3D hot bending of existing high-crystallization or fully crystallized microcrystalline glass.

[0057] 2. The flat grinding and polishing in the preparation process of 3D microcrystalline glass are carried out before 3D hot bending as needed. The flat grinding and polishing speed of 3D microcrystalline glass is related to the hardness. The greater the hardness, the greater the difficulty of flat grinding and polishing, and the longer the time required. The present invention uses partially crystallized microcrystalline glass for flat grinding and polishing, and the hardness is lower than that of fully crystallized microcrystalline glass. The difficulty of flat grinding and polishing of glass sheets is reduced, and the time required is reduced.

[0058] 3. The optical performance of the 3D glass-ceramics of the present invention has been improved. Since the softening and molding temperature of existing fully crystallized glass-ceramics is generally above 700°C, the crystals in the glass-ceramics will continue to grow during the hot bending process at a temperature above 700°C, and the remaining glass will crystallize again. There is a problem of excessive crystallization, which leads to a significant decrease in the optical performance of the glass-ceramics after hot bending. The optical performance of the 3D glass-ceramics of the present invention is an average transmittance of 88-93% at a wavelength of 380-780nm and an average transmittance of 65-91.5% at a wavelength of 360-400nm. The absolute value of the b value (yellow-blue value) of the 3D glass-ceramics when the thickness is 0.7mm is 0.1-3.5.

[0059] 4. The control rate of the dimensional accuracy of the 3D microcrystalline glass of the present invention is improved. When partially crystallized microcrystalline glass is used for 3D heat bending, the glass continues to crystallize when heated to reach the target crystallinity. Although the glass will deform while being heat-bent and crystallized during this process, the deformation becomes smaller due to the reduction of the crystallization process during 3D heat bending, which is conducive to controlling the dimensional accuracy of the 3D microcrystalline glass after heat bending.

[0060] 5. The yield rate of the 3D glass-ceramics of the present invention is improved. If nucleated glass or glass with low initial crystallinity is used as the raw material for 3D hot bending, the raw material requires a large amount of crystallization in a short period of time during hot bending. The raw materials between different batches are affected by too many variable factors in the 3D hot bending process, which will lead to poor stability in crystal size, crystal type, and crystal ratio between different batches. When partially crystallized glass-ceramics is used for 3D hot bending, its crystallinity is relatively high, and the amount of crystal growth during the hot bending process is small, which reduces the influence of variable factors, making it easier to control the stability of different batches of 3D glass-ceramics and improve the yield rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is the XRD pattern of the glass brick obtained after annealing and before nucleation in step 2 of Example 25;

[0062] Figure 2 is the XRD pattern of the partially crystallized glass original sheet obtained in step 4 of Example 25;

[0063] Figure 3 is the XRD pattern of the partially crystallized glass original sheet obtained in step 4 of Example 26;

[0064] Figure 4 This is the XRD diagram of the partially crystallized glass original sheet obtained in step 4 in Example 30. DETAILED DESCRIPTION

[0065] The present invention provides a 3D microcrystalline glass, characterized in that the crystallinity of the 3D microcrystalline glass is 14-100wt%; and the average particle size of the crystals of the 3D microcrystalline glass is 10-100nm.

[0066] Preferably, the crystallinity of the 3D glass-ceramics is 14-30wt%, or the crystallinity of the 3D glass-ceramics is 50-100wt%; or the crystallinity of the 3D glass-ceramics is 31-49wt%; or the crystallinity of the 3D glass-ceramics is 10-20wt%; 21-30wt%; 31-40wt%; 41-50wt%; 51-60wt%; 61-70wt%; 71-80wt%; 81-90wt%; 91-100wt%.

[0067] Alternatively, the average particle size of the crystals of the 3D glass-ceramics is 15-30 nm;

[0068] Alternatively, the thickness of the 3D glass-ceramics is 0.02-5 mm, and preferably, the thickness of the 3D glass-ceramics is 0.35-1.2 mm.

[0069] Preferably, the average transmittance of the 3D glass-ceramics at a wavelength of 380-780 nm is 88-93%, preferably 90-91.5%;

[0070] Alternatively, the average transmittance of the 3D glass-ceramics at a wavelength of 360-400 nm is 65-91.5%, preferably 79-91%, and more preferably 85-91%.

[0071] Preferably, the absolute value of the b value (yellow-blue value) of the 3D glass-ceramics when the thickness is 0.7 mm is 0.1-3.5, preferably 0.3-1.5;

[0072] Alternatively, the haze of the 3D glass-ceramics is 0.07-1.0%, preferably 0.07-0.5%.

[0073] Preferably, the crystalline phase of the 3D microcrystalline glass is one or more of lithium silicate, lithium disilicate, β-quartz, β-quartz solid solution, petalite, β-spodumene, β-spodumene solid solution, nepheline, cordierite, mullite, apatite, zirconium dioxide, gahnite, magnesia-aluminum spinel and rutile.

[0074] Preferably, the 3D glass-ceramics contains the following proportions of oxides in mol%:

[0075]

[0076] Wherein, the rare earth oxide is selected from La 2 O 3 ,Eu 2 O 3 , Pr 6 O 11 , Nd 2 O 3 , Er 2 O 3 and Dy 2 O 3 One or more of the following.

[0077] Preferably, the 3D glass-ceramics contains SiO in mol%. 2 and Al 2 O 3 The total amount is greater than 60%; preferably 68-80%;

[0078] Alternatively, containing Na 2 O+Li 2 The content of O is 7% to 30% by mol%, preferably 10% to 26%.

[0079] Preferably, the 3D glass-ceramics includes a nucleating agent, which is calculated as oxide, fluoride or single substance, and the nucleating agent includes P 2 O 5 , TiO 2 , ZrO 2 ,Cr 2 O 3 , CaF 2 , LiF, NaF, KF, Y 2 O 3 , Au, Ag and Cu, one or more thereof; preferably P 2 O 5 , TiO 2 and ZrO 2 One or more of the following.

[0080] Preferably, the 3D glass-ceramics includes a clarifier, and the clarifier includes NaCl, Na 2 SO 4 , SnO 2 , As 2 O 3 , Sb 2 O 3 , NaNO 3 , KNO 3 , CeO 2 and (NH 4 ) 2 SO 4 One or more of; preferably NaCl, SnO 2 , NaNO 3 and CeO 2 One or more of the following.

[0081] Preferably, the crystallized glass original sheet of the 3D microcrystalline glass is a glass sheet having crystals with an average particle size of 5-50 nm after nucleation and crystallization treatment.

[0082] Preferably, the crystallized glass original sheet of the 3D microcrystalline glass is a glass sheet with a crystallinity of 5-90wt% after nucleation and crystallization treatment. Preferably, the crystallinity is 5-10wt%, 11-15wt%, 16-20wt%, 21-25wt%, 26-30wt%, 31-35wt%, 36-40wt%, 41-45wt%, 46-50wt%, 51-55wt%, 56-60wt%, 61-65wt%, 66-70wt%, 71-75wt%, 76-80wt%, 81-85wt%, 86-90wt%, 91-95wt%, 96-100wt%, 15-29wt%, 30-75wt%, 76-90wt%, and / or 30-55wt%.

[0083] Preferably, the drop height of the 3D glass-ceramics after chemical strengthening is greater than 1.5 m, and preferably, the Vickers hardness is greater than 650 under a force load of 300 N for 10 s.

[0084] When the thickness of the 3D glass-ceramics is 0.65 mm, after chemical strengthening, the whole device is dropped onto a bottom plate whose medium is a marble material with a load of 160 g and the drop height is greater than 1.5 m. Preferably, the Vickers hardness is greater than 650 under a load of 300 N for 10 seconds.

[0085] The present invention also provides a method for preparing the above-mentioned 3D glass-ceramics, wherein the preparation method comprises the following steps:

[0086] Step 1: Mix the raw materials for preparing 3D glass-ceramics, melt them, cool them, and perform annealing to obtain a glass substrate;

[0087] Step 2: performing a nucleation treatment on the glass substrate obtained in step 1; wherein the glass substrate may be cut as required before or after the nucleation treatment;

[0088] Step 3: crystallizing the glass substrate after nucleation in step 2;

[0089] Step 4: Cutting the crystallized glass substrate as needed to obtain crystallized glass raw material;

[0090] Step 5: Perform 3D heat bending on the crystallized glass raw material to obtain a 3D micro-ceramic glass sample;

[0091] The 3D hot bending process in step 5 is also accompanied by a crystallization process.

[0092] Wherein, the crystallized glass material in steps 4 and 5 may be a partially crystallized glass material.

[0093] Preferably, the method may further include the step of subjecting the 3D glass-ceramics sample to chemical strengthening treatment to obtain a 3D glass-ceramics finished product.

[0094] Preferably, in step 1, the melting temperature is 1350-1700°C; preferably, the melting temperature is 1400-1650°C; more preferably, the temperature is cooled to 500-1000°C after melting.

[0095] Preferably, in the step 1, the melting time is 1-5 hours; preferably, in the step 3, crystallization treatment is performed after keeping warm at 500-900°C for 5-300 minutes; further preferably, in the step 3, one or more of trimming, CNC machine tool processing, rough grinding and / or polishing treatments are also included to obtain the crystallized glass raw material.

[0096] Preferably, the amount of the nucleating agent added in step 1 is 1-9 mol% of the total amount of the nucleating agent and the microcrystalline glass oxide, and more preferably the amount of the nucleating agent is 2-5 mol%.

[0097] Preferably, the amount of the clarifier added in step 1 is 0-4 wt %, preferably 0.1-2 wt %, of the total mass of the nucleating agent and the glass-ceramic oxide.

[0098] Preferably, in step 2, the temperature of the nucleation treatment is 450-800°C, and the time of the nucleation treatment is 30-360 minutes; further preferably, the temperature of the nucleation treatment is 520-570°C, and the time of the nucleation treatment is 120-300 minutes.

[0099] Preferably, in step 3, the temperature of the crystallization treatment is 550-900° C., and the time of the crystallization treatment is 5-300 min;

[0100] Preferably, the crystallization temperature is 600-850°C, and the crystallization time is 10-240 minutes.

[0101] More preferably, the temperature of the crystallization treatment is 600-750° C., and the time of the crystallization treatment is 10-150 min.

[0102] Preferably, the hot bending process in step 5 includes a preheating station, a hot pressing station and a cooling station.

[0103] Preferably, the number of preheating stations is 1-30, preferably 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 1, 2, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30; preferably 2-4; the number of hot pressing stations is 1-30, preferably 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 1, 2, 13, 14, 15 ,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30; preferably 1-3; the cooling stations include 1-30, preferably 1,2,3,4,5,6,7,8,9,10,11,1,2,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30; preferably 2-4.

[0104] Preferably, the temperature of the preheating station is 300-850°C; the temperature of the hot pressing station is 600-920°C and the pressure is 0-6MPa; the temperature of the cooling station is 200-650°C.

[0105] Preferably, the working time of the preheating station is 20-800 seconds; the working time of the hot pressing station is 20-800 seconds; and the working time of the cooling station is 20-800 seconds;

[0106] Preferably, the working time of the preheating station is 60-600 seconds; the working time of the hot pressing station is 60-480 seconds, and the working time of the cooling station is 60-600 seconds.

[0107] The present invention also provides 3D microcrystalline glass prepared by the preparation method.

[0108] Preferably, the 3D glass-ceramics is characterized in that the 3D glass-ceramics is transparent or opaque; preferably, the 3D glass-ceramics is curved or flat.

[0109] The present invention also provides the use of the above-mentioned 3D microcrystalline glass or the 3D microcrystalline glass described in claim 24 or 25 in mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.

[0110] Glossary:

[0111] 3D glass-ceramics: glass-ceramics with non-planar upper and lower surfaces;

[0112] 2D glass-ceramics: glass-ceramics with both upper and lower surfaces being flat;

[0113] 2.5D glass-ceramic: glass-ceramic with one surface being flat and the other being non-flat;

[0114] Crystallinity: Glass-ceramics contain crystalline phase and glass phase. The percentage of the mass of the crystalline phase to the total mass of the glass-ceramics is the crystallinity.

[0115] Transmittance: The ratio of the radiant energy projected and transmitted through an object to the total radiant energy projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side;

[0116] Average transmittance: In the specified wavelength range, the transmittance at each wavelength is measured at intervals of 10nm, and the value is obtained by dividing the sum of the transmittances at each wavelength by the number of transmittances at each wavelength measured. For example, the average transmittance calculation method for a wavelength of 360-400nm is as follows: the transmittances at wavelengths of 360nm, 370nm, 380nm, 390nm, and 400nm are measured respectively, and the number of transmittances measured at 360-400nm is 5. The sum of the above transmittances is divided by 5 to obtain the average transmittance of a wavelength of 360-400nm;

[0117] Nucleation: Through heat treatment, the nucleating material in the glass grows into a crystal nucleus of about 5nm;

[0118] Crystallization: Glass grows a certain crystal based on the crystal nucleus through heat treatment;

[0119] Average crystal particle size: the average value of the length of the crystal grains in the microcrystalline glass observed at a magnification of 100,000 to 1,000,000 times. It is measured by observation using a transmission electron microscope (model: ThermoFisher Scientific (formerly FEI) Talos F200S). The measurement is equivalent to taking an enlarged photo of the crystal grains in a certain part. There are limited crystal grains in the area of ​​the enlarged photo. The size of the limited crystal grains is marked according to the scale, and then the average is calculated. In the embodiment of the present invention, the magnification is 500,000 times during measurement.

[0120] b value: indicates the yellow-blue value of the material. In the present invention, the b value is the b value of transmitted light. A positive b value indicates that the material is blue. It is measured using a chromatograph (model CM-3600A).

[0121] Haze: The percentage of the transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity. Measured using a chromatograph (model CM-3600A).

[0122] The optical performance of the 3D microcrystalline glass when the thickness is 0.65mm is that the absolute value of the b value under the D65 light source is 0.1-3.5, and the preferred absolute value of the b value under the D65 light source is 0.3-1.5; the light transmittance at a wavelength of 360nm is greater than or equal to 80%, and the preferred wavelength transmittance at 360nm is greater than or equal to 85%.

[0123] Nucleating agents include but are not limited to P 2 O 5 , TiO 2 , ZrO 2 ,Cr 2 O 3 , CaF 2 , LiF, NaF, KF, Y 2 O 3 , Au, Ag and Cu, etc.

[0124] When partially crystallized glass-ceramics is crystallized by thermal bending, the crystallization speed is controllable, which is conducive to the growth of crystals with a particle size below 100nm. Through process control, the average particle size of the precipitated crystals can be guaranteed to be 10-100nm, thereby improving the optical properties of 3D glass-ceramics.

[0125] In other specific embodiments, in the 3D hot bending process of partially crystallized glass-ceramics, crystallization and 3D hot bending are carried out simultaneously, and the hot bending time is generally within 30 minutes. Some embodiments show that partially crystallized glass-ceramics, under suitable processes, can achieve a crystallinity of more than 80wt% after 10-20 minutes of 3D hot bending, and the optical properties meet the requirements.

[0126] The crystalline phase of the 3D microcrystalline glass includes lithium silicate, lithium disilicate, β-quartz, β-quartz solid solution, petalite, β-spodumene, β-spodumene solid solution, nepheline, cordierite, mullite, apatite, zirconium dioxide, ganese spinel, magnesium aluminum spinel and rutile, etc.

[0127] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments.

[0128] The manufacturers of the raw materials and equipment used in this example, as well as the equipment and analysis methods used in the product analysis are described below. The chemical substances described without being marked are of the chemical purity level of conventional reagents.

[0129] The information of the raw materials used in the examples and comparative examples is shown in Table 1 below.

[0130] Table 1 Information of raw materials and instruments used in the present invention

[0131]

[0132]

[0133]

[0134] Example

[0135] The hot bending process in the embodiment is shown in Table 2. For example, when the process number is 1, the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 430°C, the temperature of the second preheating station is 500°C, the temperature of the third preheating station is 600°C, and the temperature of the fourth preheating station is 680°C. The temperature of the first hot pressing station is 800°C, the upper pressure is 0.4MPa, and the lower pressure is 0.4MPa; the temperature of the second hot pressing station is 810°C, the upper pressure is 0.4MPa, and the lower pressure is 0.4MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0.4MPa, and the lower pressure is 0.4MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 20s.

[0136] For example, the hot bending process with serial number 12 is: the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 430℃, the temperature of the second preheating station is 500℃, the temperature of the third preheating station is 700℃, and the temperature of the fourth preheating station is 850℃. The temperature of the first hot pressing station is 780℃, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 760℃, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 600℃, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa. The temperature of the first cooling station is 450℃, and the temperature of the second cooling station is 300℃. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s. This is listed.

[0137] Table 2 Hot bending process table in the embodiments and comparative examples

[0138]

[0139] Example 1 Preparation method of 3D glass-ceramics:

[0140] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 62.00%;Al 2 O 3 17.00%; MgO 2.50%; Na 2 O 2.50%; Li2 O 10.00%; B 2 O 3

[0141] 2.00%, Rare Earth Oxide La 2 O 3 0.8%, nucleating agent (containing 2.00% P 2 O 5 ; 1.20% ZrO 2 ), and 0.8wt% of the total weight of the nucleating agent and the raw materials for preparation as a clarifier NaCl, the total weight of the above raw materials is 1713.6g), after being fully mixed, melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1650°C, the melting time is 5h, and poured into a mold made of ASTMSA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0142] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 620°C for 5h, then reduce the temperature to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 760°C, and the nucleation treatment time is 120min;

[0143] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 790° C. for 10 minutes to obtain partially crystallized glass bricks;

[0144] Step 4: After the partially crystallized glass bricks are trimmed by a grinder and polisher, they are cut into pieces using a multi-wire cutting machine, and processed into glass pieces with a length, width and thickness of 158*75*0.65mm by a CNC machine tool. Then, they are roughly ground and polished using a flat grinder and a polisher respectively to obtain partially crystallized glass original pieces. After measurement, the crystallinity is 10wt%.

[0145] Step 5: Perform 3D hot bending on part of the crystallized glass original sheet; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 430°C, the temperature of the second preheating station is 500°C, the temperature of the third preheating station is 600°C, and the temperature of the fourth preheating station is 680°C. The temperature of the first hot pressing station is 800°C, the upper pressure is 0.4MPa, and the lower pressure is 0.4MPa; the temperature of the second hot pressing station is 810°C, the upper pressure is 0.4MPa, and the lower pressure is 0.4MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0.4MPa, and the lower pressure is 0.4MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 20s. (That is, the hot bending process numbered 1 in Table 2 is used) to obtain a 3D microcrystalline glass sample 1.

[0146] The above-mentioned 3D microcrystalline glass sample 1 was tested using a X-ray diffractometer, with the instrument setting voltage of 40mV, current of 30mA, test range of 10-50°, scanning speed of 1° / min, and step size of 0.02° / step. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 1 was 15wt%, the precipitated crystalline phase was β-spodumene, and the average particle size of the crystal was 37nm. When the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 1 was 2.30; the light transmittance of the wavelength of 360nm was 76.30%, the average light transmittance of the wavelength of 380-780nm was 88.20%, the average light transmittance of the wavelength of 360-400nm was 80.10%, and the haze was 0.40%.

[0147] Step 6: The 3D glass-ceramics obtained in step 5 is subjected to chemical strengthening treatment by immersing the glass in molten 100wt% NaNO at a temperature of 430°C. 3 After being in the solution for 8 hours, a 3D microcrystalline glass product 1 is finally obtained.

[0148] Example 2 Preparation method of 3D glass-ceramics:

[0149] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 64.00%;Al 2 O 3 17.00%;Na 2 O 2.50%; Li 2 O 12.5%; B 2 O 3 2.00%, nucleating agent (0.80% P 2 O 5; 1.20% ZrO 2 ), and 0.8wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1713.6g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1650°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0150] Step 2 and step 3 are the same as in Example 1;

[0151] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that of Example 1. After measurement, the crystallinity is 13wt%;

[0152] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, and adopt the heat bending process numbered 1 in Table 2 (refer to Example 1) to obtain a 3D microcrystalline glass sample 2.

[0153] The above-mentioned 3D microcrystalline glass sample 2 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 2 after heat bending was 24wt%, the precipitated crystal phase was β-spodumene, and the average particle size of the crystal was 27nm. It was determined that when the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 2 was 3.10; the light transmittance at a wavelength of 360nm was 76.00%, the average light transmittance at a wavelength of 380-780nm was 88.00%, the average light transmittance at a wavelength of 360-400nm was 78.00%, and the haze was 0.43%.

[0154] Step 6: The 3D microcrystalline glass obtained in step 5 after heat bending is subjected to chemical strengthening treatment, and the treatment conditions are the same as those in Example 1, and finally a 3D microcrystalline glass finished product 2 is obtained.

[0155] Example 3 Preparation method of 3D microcrystalline glass:

[0156] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 63.64%;Al 2 O 3 16.03%; Li 2 O 16.03%; B 2 O 3 2.00%, nucleating agent (0.80% P 2 O 5 ;

[0157] 1.50% ZrO 2), and 0.8wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1713.6g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0158] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 610°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 705°C, and the nucleation treatment time is 120min;

[0159] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 775° C. for 10 minutes to obtain partially crystallized glass bricks;

[0160] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 9wt%.

[0161] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet; adopt the heat bending process numbered 1 in Table 2 (refer to Example 1) to obtain a 3D microcrystalline glass sample 3.

[0162] The above-mentioned 3D microcrystalline glass sample 3 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 3 after hot bending was 18wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 24nm. It was measured that when the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 3 was 1.21; the light transmittance of the wavelength of 360nm was 83.71%, the average light transmittance of the wavelength of 380-780nm was 90.22%, the average light transmittance of the wavelength of 360-400nm was 84.56%, and the haze was 0.16%.

[0163] Example 4 Preparation method of 3D glass-ceramics:

[0164] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 66.63%;Al 2 O 3 15.13%; MgO 4.76%; Na 2 O 1.55%; Li 2 O 8.65%; Rare earth oxide La 2 O3 0.81%, nucleating agent (0.67% P 2 O 5 ; 1.30% ZrO 2 , Y 2 O 3 0.50%), and 0.8wt% of NaCl accounting for the total weight of the nucleating agent and the raw materials, the total weight of the above raw materials is 1713.6g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0165] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 610°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 720°C, and the time of the nucleation treatment is 120min;

[0166] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 780° C. for 10 minutes to obtain partially crystallized glass bricks;

[0167] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 11 wt%.

[0168] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet; adopt the heat bending process numbered 1 in Table 2 (refer to Example 1) to obtain a 3D microcrystalline glass sample 4.

[0169] The above-mentioned 3D microcrystalline glass sample 4 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 4 after heat bending was 23wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 27nm. It was determined that when the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 4 was 1.48; the light transmittance at a wavelength of 360nm was 80.06%, the average light transmittance at a wavelength of 380-780nm was 89.5%, the average light transmittance at a wavelength of 360-400nm was 83.50%, and the haze was 0.25%.

[0170] Step 6: The 3D glass-ceramics obtained in step 5 is subjected to chemical strengthening treatment by immersing the glass in molten 100wt% NaNO at a temperature of 450°C. 3 After being in the solution for 7 hours, a 3D microcrystalline glass product 4 is finally obtained.

[0171] Example 5 Preparation method of 3D glass-ceramics:

[0172] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 66.96%;Al 2 O 3 14.20%; MgO 4.79%; Na 2 O 0.56%; Li 2 O 9.70%; Rare earth oxide Er 2 O 3 0.81%, nucleating agent (1.68% P 2 O 5 ; 1.30% ZrO 2 ), and 0.4wt% of NaCl and 0.4wt% of SnO 2 As a clarifier, the above raw materials have a total weight of 1713.6 g, are fully mixed and melted in a high-temperature lifting furnace, the melting and molding temperature is 1630°C, the melting time is 5 hours, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0173] Step 2 and step 3 are the same as in Example 4;

[0174] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 16 wt%.

[0175] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet; adopt the heat bending process numbered 1 in Table 2 (refer to Example 1) to obtain 3D microcrystalline glass sample 5.

[0176] The above-mentioned 3D microcrystalline glass sample 5 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 5 after hot bending was 33wt%, the precipitated crystal phases were β-quartz solid solution and β-spodumene, and the average particle size of the crystal was 22nm. It was determined that when the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 5 was 3.24; the light transmittance at a wavelength of 360nm was 72.00%, the average light transmittance at a wavelength of 380-780nm was 88.90%, the average light transmittance at a wavelength of 360-400nm was 78.60%, and the haze was 0.54%.

[0177] Example 6 Preparation method of 3D glass-ceramics:

[0178] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 66.95%;Al 2 O 3 14.20%; MgO 2.29%; Na 2 O 1.56%; ZnO 1.00%, Li 2 O

[0179] 9.70%; Rare earth oxide La 2 O 3 0.81%, nucleating agent (1.68% P 2 O 5 ; 1.31% ZrO 2 ; 0.5% Y 2 O 3 ), and 0.8wt% of the total weight of the nucleating agent and the raw materials for preparation as a clarifier NaCl, the total weight of the above raw materials is 1713.6g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTMSA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0180] Step 2 is the same as in Example 4;

[0181] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 765° C. for 20 minutes to obtain partially crystallized glass bricks;

[0182] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 12 wt%.

[0183] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, and adopt the heat bending process numbered 1 in Table 2 (refer to Example 1) to obtain a 3D microcrystalline glass sample 6.

[0184] The above-mentioned 3D microcrystalline glass sample 6 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 6 after hot bending was 23wt%, the precipitated crystal phases were β-quartz solid solution and β-spodumene, and the average particle size of the crystal was 30nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 3.4; the light transmittance of the wavelength of 360nm was 66.30%, the average light transmittance of the wavelength of 380-780nm was 88.30%, the average light transmittance of the wavelength of 360-400nm was 76.20%, and the haze was 0.96%.

[0185] Example 7 Preparation method of 3D glass-ceramics:

[0186] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 66.42%;Al 2 O 3 14.09%; MgO 4.75%; Na 2 O 1.55%; Li 2 O 9.62%, nucleating agent (0.67% P 2 O 5 ; 1.3% ZrO 2 ; 1.6% TiO 2 ), and NaCl accounting for 0.8wt% of the total mass of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1713.6g, and after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0187] Step 2 is the same as in Example 4;

[0188] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 750° C. for 20 minutes to obtain partially crystallized glass bricks;

[0189] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 17 wt%.

[0190] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 1 in Table 2 (refer to Example 1) to obtain a 3D microcrystalline glass sample 7.

[0191] The above-mentioned 3D microcrystalline glass sample 7 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 7 after heat bending was 34wt%, the precipitated crystalline phase was β-quartz solid solution, and the average particle size of the crystal was 24nm. It was determined that when the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 7 was 1.20; the light transmittance at a wavelength of 360nm was 83.10%, the average light transmittance at a wavelength of 380-780nm was 90.28%, the average light transmittance at a wavelength of 360-400nm was 84.62%, and the haze was 0.15%.

[0192] Step 6: The 3D glass-ceramics obtained in step 5 is subjected to chemical strengthening treatment by immersing the glass in molten 100wt% NaNO at a temperature of 430°C. 3 After being in the solution for 9 hours, a 3D microcrystalline glass product 7 is finally obtained.

[0193] Example 8 Preparation method of 3D glass-ceramics:

[0194] Step 1: Prepare and weigh the raw materials for glass preparation, which contain the following components in molar percentage: SiO 2 66.95%;Al 2 O 3 13.20%; CaO 1.0%; MgO3.79%; Na 2 O 1.56%; Li 2 O 9.70%; nucleating agent (1.68% P 2 O 5 ; 1.51% ZrO 2 , 0.61% TiO 2 , and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0195] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 570°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 715°C, and the nucleation treatment time is 200min;

[0196] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 820° C. for 10 minutes to obtain partially crystallized glass bricks;

[0197] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 28wt%.

[0198] Step 5: Perform 3D hot bending on part of the crystallized glass original sheet; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 480°C, the temperature of the second preheating station is 635°C, the temperature of the third preheating station is 685°C, and the temperature of the fourth preheating station is 715°C. The temperature of the first hot pressing station is 745°C, the upper pressure is 0.3MPa, and the lower pressure is 0.6MPa; the temperature of the second hot pressing station is 760°C, the upper pressure is 0MPa, and the lower pressure is 0.MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 80s. (That is, using the hot bending process numbered 8 in Table 2) to obtain 3D microcrystalline glass sample 8.

[0199] The above-mentioned 3D microcrystalline glass sample 8 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 8 after hot bending was 45wt%, the precipitated crystalline phases were β-quartz solid solution and β-spodumene, and the average particle size of the crystal was 37nm. When the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 8 was 2.90; the light transmittance at a wavelength of 360nm was 76.11%, the average light transmittance at a wavelength of 380-780nm was 88.10%, the average light transmittance at a wavelength of 360-400nm was 78.80%, and the haze was 0.63%.

[0200] Example 9 Preparation method of 3D microcrystalline glass:

[0201] Step 1: Prepare and weigh the raw materials for glass preparation, which contain the following components in molar percentage: SiO 2 66.96%;Al 2 O 3 13.20%; MgO 5.79%; Na 2 O 1.26%; Li 2 O 8.00%; B 2 O 3

[0202] 1.00%; Rare earth oxide Er 2 O 3 0.9%, nucleating agent (1.68% P 2 O 5 ; 1.21% ZrO 2), and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0203] Step 2 and step 3 are the same as in Example 8;

[0204] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 19wt%.

[0205] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 8 in Table 2 (refer to Example 8) to obtain a 3D microcrystalline glass sample 9.

[0206] The above-mentioned 3D microcrystalline glass sample 9 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 9 after hot bending was 32wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 24nm. It was determined that when the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 9 was 1.30; the light transmittance at a wavelength of 360nm was 82.10%, the average light transmittance at a wavelength of 380-780nm was 89.40%, the average light transmittance at a wavelength of 360-400nm was 85.20%, and the haze was 0.21%.

[0207] Example 10 Preparation method of 3D glass-ceramics:

[0208] Step 1: Prepare and weigh the raw materials for glass preparation, which contain the following components in molar percentage: SiO 2 71.65%;Al 2 O 3 13.20%; MgO 2.79%; Na 2 O 0.56%; Li 2 O 8.00%; Rare earth oxide Er 2 O 3 0.61%, nucleating agent (1.68% P 2 O 5 ; 1.51% ZrO 2), and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0209] Step 2 is the same as in Example 8;

[0210] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 800° C. for 10 minutes to obtain partially crystallized glass bricks;

[0211] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 20wt%.

[0212] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 8 in Table 2 (refer to Example 8) to obtain a 3D microcrystalline glass sample 10.

[0213] The above-mentioned 3D microcrystalline glass sample 10 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 10 after heat bending was 37wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 27nm. It was determined that when the light source was limited to D65, the absolute value of the b value was 1.60; the light transmittance at a wavelength of 360nm was 81.13%, the average light transmittance at a wavelength of 380-780nm was 89.60%, the average light transmittance at a wavelength of 360-400nm was 82.80%, and the haze was 0.19%.

[0214] Example 11 Preparation method of 3D glass-ceramics:

[0215] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 70.65%;Al 2 O 3 13.20%; MgO 2.79%; Na 2 O 1.56%; Li 2 O 8.00%; Rare earth oxide La 2 O 3 0.61%, nucleating agent (1.68% P 2 O 5 ; 1.51% ZrO 2), and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0216] Step 2 and step 3 are the same as in Example 10;

[0217] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 21wt%.

[0218] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 8 in Table 2 (refer to Example 8) to obtain a 3D microcrystalline glass sample 11.

[0219] The above-mentioned 3D microcrystalline glass sample 11 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 11 after hot bending was 41wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 22nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 1.10; the light transmittance of the wavelength of 360nm was 82.40%, the average light transmittance of the wavelength of 380-780nm was 90.60%, the average light transmittance of the wavelength of 360-400nm was 85.30%, and the haze was 0.13%.

[0220] Example 12 Preparation method of 3D glass-ceramics:

[0221] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 70.65%;Al 2 O 3 12.92%; MgO 2.42%; ZnO 0.80%; Na 2 O 1.05%; Li 2 O

[0222] 8.25%; Rare earth oxide La 2 O 3 1.22%, nucleating agent (1.37% P 2 O 5 ; 1.32% Y 2 O 3 ), and 0.3wt% of NaNO 3 and 0.4wt% As 2 O3 As a clarifier, the above raw materials have a total weight of 1711.9 g, are fully mixed and melted in a high-temperature lifting furnace, the melting and molding temperature is 1630°C, the melting time is 5 hours, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0223] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 570°C for 5h, decreasing to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 700°C, and the nucleation treatment time is 200min;

[0224] Step 3 is the same as in Example 5;

[0225] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 25wt%.

[0226] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 8 in Table 2 (refer to Example 8) to obtain a 3D microcrystalline glass sample 12.

[0227] The above-mentioned 3D microcrystalline glass sample 12 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 12 after hot bending was 43wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 24nm. It was determined that when the light source was limited to D65, the absolute value of the b value was 1.15; the light transmittance at a wavelength of 360nm was 83.68%, the average light transmittance at a wavelength of 380-780nm was 90.56%, the average light transmittance at a wavelength of 360-400nm was 86.30%, and the haze was 0.17%.

[0228] Step 6: The 3D microcrystalline glass obtained in step 5 after heat bending is subjected to chemical strengthening treatment. The chemical strengthening conditions are the same as those in Example 7, and finally a 3D microcrystalline glass product 12 is obtained.

[0229] Example 13 Preparation method of 3D glass-ceramics:

[0230] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 71.15%;Al 2 O 3 12.70%; MgO 2.79%; Na 2 O 0.56%; Li 2 O 8.00%; B 2 O3

[0231] 1.00%, Rare Earth Oxide Nd 2 O 3 0.61%, nucleating agent (1.68% P 2 O 5 ; 1.51% CaF 2 ), and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, after being fully mixed, they are melted and formed in a high-temperature lifting furnace, the temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0232] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 570°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 710°C, and the nucleation treatment time is 200min;

[0233] Step 3 is the same as in Example 10;

[0234] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 18 wt%.

[0235] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 8 in Table 2 (refer to Example 8) to obtain a 3D microcrystalline glass sample 13.

[0236] The above-mentioned 3D microcrystalline glass sample 13 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 13 after hot bending was 34wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 35nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 1.75; the light transmittance of the wavelength of 360nm was 81.03%, the average light transmittance of the wavelength of 380-780nm was 89.00%, the average light transmittance of the wavelength of 360-400nm was 82.30%, and the haze was 0.23%.

[0237] Example 14 Preparation method of 3D glass-ceramics:

[0238] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 68.00%;Al 2 O 312.00%; MgO 3.5%; Na 2 O 0.50%; Li 2 O 10.00%; B 2 O 3 3.00%, nucleating agent (2.00% P 2 O 5 ; 1.00% Y 2 O 3 ), and 0.2wt% NaCl, 0.2wt% SnO 2 and 0.2wt% CeO 2 As a clarifier, the above raw materials have a total weight of 1711.9 g, are fully mixed and melted in a high-temperature lifting furnace, the melting and molding temperature is 1630°C, the melting time is 5 hours, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0239] Step 2 is the same as in Example 13;

[0240] Step 3 is the same as in Example 1;

[0241] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 35wt%.

[0242] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 8 in Table 2 (refer to Example 8) to obtain a 3D microcrystalline glass sample 14.

[0243] The above-mentioned 3D microcrystalline glass sample 14 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 14 after hot bending was 62wt%, the precipitated crystal phase was β-quartz solid solution + petalite, and the average particle size of the crystal was 27nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 1.11; the light transmittance of the wavelength of 360nm was 84.20%, the average light transmittance of the wavelength of 380-780nm was 90.90%, the average light transmittance of the wavelength of 360-400nm was 85.80%, and the haze was 0.22%.

[0244] Example 15 Preparation method of 3D glass-ceramics:

[0245] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 66.95%;Al 2 O 311.20%; CaO 1.20%; MgO 4.59%; Na 2 O 1.26%; Li 2 O

[0246] 9.00%; B 2 O 3 2.00%, Rare Earth Oxide Nd 2 O 3 0.61%, nucleating agent (1.68% P 2 O 5 ; 1.51% ZrO 2 ), and 0.6wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1710.2g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1630°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0247] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 550°C for 5h, and then reduce to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 690°C, and the nucleation treatment time is 200min;

[0248] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 750° C. for 30 minutes to obtain partially crystallized glass bricks;

[0249] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 32 wt%.

[0250] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 8 in Table 2 (refer to Example 8) to obtain a 3D microcrystalline glass sample 15.

[0251] The above-mentioned 3D microcrystalline glass sample 15 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 15 after hot bending was 53wt%, the precipitated crystal phase was β-quartz solid solution + petalite, and the average particle size of the crystal was 24nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.70; the light transmittance of the wavelength of 360nm was 85.22%, the average light transmittance of the wavelength of 380-780nm was 91.20%, the average light transmittance of the wavelength of 360-400nm was 87.50%, and the haze was 0.16%.

[0252] Example 16 Preparation method of 3D glass-ceramics:

[0253] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 65.10%;Al 2 O 3 8.51%;Na 2 O 1.00%; Li 2 O 20.83%; B 2 O 3 1.52%, nucleating agent (0.82% P 2 O 5 ; 1.72% ZrO 2 ; 0.5% NaF), and 0.3wt% NaNO accounting for the total mass of the nucleating agent and the raw materials for preparation 3 and 0.3wt% As 2 O 3 As a clarifier, the total weight of the above raw materials is 1710.2g, which are fully mixed and melted in a high-temperature lifting furnace. The melting and molding temperature is 1620°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel.

[0254] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 550°C for 5h, and then reduce to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 670°C, and the nucleation treatment time is 200min;

[0255] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 710° C. for 100 min to obtain partially crystallized glass bricks;

[0256] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 40wt%.

[0257] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process No. 6 in Table 2. The hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. Among them, the temperature of the first preheating station is 450℃, the temperature of the second preheating station is 600℃, the temperature of the third preheating station is 650℃, and the temperature of the fourth preheating station is 710℃. The temperature of the first hot pressing station is 730℃, the upper pressure is 0.3MPa, and the lower pressure is 0.3MPa; the temperature of the second hot pressing station is 740℃, the upper pressure is 0MPa, and the lower pressure is 0MPa; the temperature of the third hot pressing station is 600℃, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450℃, and the temperature of the second cooling station is 300℃. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 60s. A 3D glass-ceramic sample 16 was obtained.

[0258] The above-mentioned 3D microcrystalline glass sample 16 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 16 after hot bending was 60wt%, the precipitated crystal phase was β-quartz solid solution + petalite, and the average particle size of the crystal was 21nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.62; the light transmittance of the wavelength of 360nm was 86.02%, the average light transmittance of the wavelength of 380-780nm was 91.10%, the average light transmittance of the wavelength of 360-400nm was 88.10%, and the haze was 0.17%.

[0259] Step 6: The 3D glass-ceramics obtained in step 5 is subjected to chemical strengthening treatment by immersing the glass in molten 100wt% NaNO at a temperature of 430°C. 3 After 11 hours in the solution, a 3D glass-ceramic product 16 is finally obtained.

[0260] Example 17 Preparation method of 3D glass-ceramics:

[0261] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 68.00%;Al 2 O 3 5.50%; CaO 0.50%; Na 2 O 1.00%; Li 2 O 21.00%; B 2 O 3 1.50%, nucleating agent (0.80% P 2 O 5 ; 1.70% ZrO 2), and 0.5wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1630°C, the melting time is 5h, and the glass bricks are poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0262] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 500°C for 5h, and then reduce the temperature to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 570°C, and the time of the nucleation treatment is 200min;

[0263] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 640° C. for 100 min to obtain partially crystallized glass bricks;

[0264] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 78wt%.

[0265] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 6 in Table 2 (refer to Example 16) to obtain a 3D microcrystalline glass sample 17.

[0266] The above-mentioned 3D microcrystalline glass sample 17 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 17 after hot bending was 91wt%, the precipitated crystal phase was β-quartz solid solution + petalite, and the average particle size of the crystal was 21nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 1.0; the light transmittance of the wavelength of 360nm was 84.32%, the average light transmittance of the wavelength of 380-780nm was 90.80%, the average light transmittance of the wavelength of 360-400nm was 86.40%, and the haze was 0.16%.

[0267] Example 18 Preparation method of 3D glass-ceramics:

[0268] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 69.14%; Al 2 O 3 5.21%; Na 2 O 0.46%; Li 2 O 21.13%; B 2 O 31.52%, nucleating agent (0.82%P 2 O 5 ; 1.72% ZrO 2 ), and 0.5wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1550°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0269] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 490°C for 5h, and then reduce the temperature to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 530°C, and the nucleation treatment time is 200min;

[0270] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 640° C. for 120 min to obtain partially crystallized glass bricks;

[0271] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 72 wt%.

[0272] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process numbered 13 in Table 2; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 450°C, the temperature of the second preheating station is 600°C, the temperature of the third preheating station is 650°C, and the temperature of the fourth preheating station is 710°C. The temperature of the first hot pressing station is 720°C, the upper pressure is 0.3MPa, and the lower pressure is 0.3MPa; the temperature of the second hot pressing station is 720°C, the upper pressure is 0MPa, and the lower pressure is 0MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s. A 3D glass-ceramic sample 18 was obtained.

[0273] The above-mentioned 3D microcrystalline glass sample 18 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 18 after hot bending was 92wt%, the precipitated crystalline phase was lithium disilicate + petalite, and the average particle size of the crystal was 18nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.43; the light transmittance of the wavelength of 360nm was 87.17%, the average light transmittance of the wavelength of 380-780nm was 92.10%, the average light transmittance of the wavelength of 360-400nm was 90.30%, and the haze was 0.11%.

[0274] Example 19 Preparation method of 3D glass-ceramics:

[0275] Steps 1-2 are exactly the same as those in Example 18;

[0276] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 630° C. for 120 min to obtain partially crystallized glass bricks;

[0277] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 60wt%;

[0278] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 13 in Table 2 (refer to Example 18) to obtain a 3D microcrystalline glass sample 19.

[0279] The above-mentioned 3D microcrystalline glass sample 19 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 19 after hot bending was 86wt%, the precipitated crystalline phase was lithium disilicate + petalite, and the average particle size of the crystal was 19nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.44; the light transmittance of the wavelength of 360nm was 87.31%, the average light transmittance of the wavelength of 380-780nm was 92.30%, the average light transmittance of the wavelength of 360-400nm was 89.50%, and the haze was 0.11%.

[0280] Example 20 Preparation method of 3D microcrystalline glass:

[0281] Steps 1-2 are exactly the same as those in Example 18;

[0282] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 625° C. for 120 min to obtain partially crystallized glass bricks;

[0283] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that of Example 1. After measurement, the crystallinity is 51wt%;

[0284] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 13 in Table 2 (refer to Example 18) to obtain a 3D microcrystalline glass sample 20.

[0285] The above-mentioned 3D microcrystalline glass sample 20 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 20 after hot bending was 73wt%, the precipitated crystalline phase was lithium disilicate + petalite, and the average particle size of the crystal was 23nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.58; the light transmittance of the wavelength of 360nm was 86.20%, the average light transmittance of the wavelength of 380-780nm was 92.10%, the average light transmittance of the wavelength of 360-400nm was 87.80%, and the haze was 0.10%.

[0286] Example 21 Preparation method of 3D glass-ceramics:

[0287] Steps 1-2 are exactly the same as those in Example 18;

[0288] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 620° C. for 120 min to obtain partially crystallized glass bricks;

[0289] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that of Example 1. After measurement, the crystallinity is 30wt%.

[0290] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 13 in Table 2 (refer to Example 18) to obtain a 3D microcrystalline glass sample 21.

[0291] The above-mentioned 3D microcrystalline glass sample 21 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 21 after hot bending was 65wt%, the precipitated crystalline phase was lithium disilicate + petalite, and the average particle size of the crystal was 25nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.62; the light transmittance of the wavelength of 360nm was 85.14%, the average light transmittance of the wavelength of 380-780nm was 91.60%, the average light transmittance of the wavelength of 360-400nm was 88.10%, and the haze was 0.15%.

[0292] Example 22 Preparation method of 3D glass-ceramics:

[0293] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 69.5%;Al 2 O 3 5.3%;Na 2 O 1.60%; Li 2 O 20.5%; B 2 O 3 0.55%, nucleating agent (0.8%P 2 O 5 ; 1.75% ZrO 2 ), and 0.5wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1550°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0294] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 480°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 560°C, and the nucleation treatment time is 200min;

[0295] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 630° C. for 100 min to obtain partially crystallized glass bricks;

[0296] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 39wt%.

[0297] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process numbered 15 in Table 2; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 450°C, the temperature of the second preheating station is 600°C, the temperature of the third preheating station is 650°C, and the temperature of the fourth preheating station is 740°C. The temperature of the first hot pressing station is 770°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 760°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s. A 3D glass-ceramic sample 22 is obtained.

[0298] The above-mentioned 3D microcrystalline glass sample 22 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 22 after hot bending was 85wt%, the precipitated crystalline phase was petalite + lithium disilicate, and the average particle size of the crystal was 19nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.42; the light transmittance of the wavelength of 360nm was 88.23%, the average light transmittance of the wavelength of 380-780nm was 92.10%, the average light transmittance of the wavelength of 360-400nm was 89.30%, and the haze was 0.15%.

[0299] Step 6: The 3D glass-ceramics obtained in step 5 is subjected to chemical strengthening treatment by immersing the glass in molten 100wt% NaNO at a temperature of 450°C. 3 After being in the solution for 9 hours, a 3D glass-ceramic product 22 is finally obtained.

[0300] Example 23 Preparation method of 3D microcrystalline glass:

[0301] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 71.80%;Al 2 O 3 4.80%; MgO 1.40%; Na 2 O 1.00%; Li 2 O 18.80%; ZnO 0.3%, nucleating agent (0.8% P 2 O 5 ; 1.1% ZrO 2), and 0.5wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1550°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0302] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 480°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 545°C, and the nucleation treatment time is 200min;

[0303] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 610° C. for 200 min to obtain partially crystallized glass bricks;

[0304] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 45wt%.

[0305] Step 5: performing 3D heat bending on a portion of the crystallized glass original sheet, using the heat bending process numbered 15 in Table 2 (refer to Example 22), to obtain a 3D micro-ceramic glass sample 23;

[0306] The above-mentioned 3D microcrystalline glass sample 23 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 23 after hot bending was 92wt%, the precipitated crystalline phase was petalite + lithium disilicate, and the average particle size of the crystal was 20nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.61; the light transmittance of the wavelength of 360nm was 85.82%, the average light transmittance of the wavelength of 380-780nm was 91.50%, the average light transmittance of the wavelength of 360-400nm was 88.00%, and the haze was 0.15%.

[0307] Step 6: The 3D microcrystalline glass obtained after heat bending in step 5 is subjected to chemical strengthening treatment, and the treatment conditions are the same as those in Example 22, and finally a 3D microcrystalline glass finished product 23 is obtained.

[0308] Example 24 Preparation method of 3D glass-ceramics:

[0309] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 69.50%;Al 2 O 3 4.25%;Na2 O 1.60%; Li 2 O 20.5%; B 2 O 3 1.60%, nucleating agent (0.8% P 2 O 5 ; 1.75% ZrO 2 ), and 0.5wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1550°C, the melting time is 5h, and the glass bricks are poured into a mold made of ASTMSA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0310] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 480°C for 5h, decreasing to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 538°C, and the nucleation treatment time is 200min;

[0311] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 620° C. for 100 min to obtain partially crystallized glass bricks;

[0312] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 43wt%.

[0313] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process numbered 14 in Table 2; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 450°C, the temperature of the second preheating station is 600°C, the temperature of the third preheating station is 650°C, and the temperature of the fourth preheating station is 720°C. The temperature of the first hot pressing station is 750°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 760°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s. A 3D glass-ceramic sample 24 was obtained.

[0314] The above 3D microcrystalline glass sample 24 was tested with light of wavelength 360nm with the absolute value of b value. A X-ray diffractometer was used, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test were analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 24 after hot bending was 82wt%, and the precipitated crystalline phase was petalite + lithium disilicate, and the average particle size of the crystal was 22nm. It was measured that when the light source was limited to D65, the absolute value of b value was 0.43; the light transmittance of wavelength 360nm was 88.17%, the average transmittance of wavelength 380-780nm was 92.60%, the average transmittance of wavelength 360-400nm was 89.60%, and the haze was 0.11%.

[0315] Step 6: The 3D microcrystalline glass obtained after heat bending in step 5 is subjected to chemical strengthening treatment, and the treatment conditions are the same as those in Example 22, and finally a 3D microcrystalline glass finished product 24 is obtained.

[0316] Example 25 Preparation method of 3D glass-ceramics:

[0317] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 68.76%;Al 2 O 3 4.13%; MgO 0.98%, ZnO 0.98%, Na 2 O 0.45%; Li 2 O20.71%; B 2 O 3 1.49%, nucleating agent (0.81% P 2 O 5 ; 1.69% ZrO 2 ), and 0.5wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1550°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0318] Step 2: After cooling the glass bricks obtained in step 1 to 800°C, transfer them to an annealing furnace for annealing (annealing process is 480°C for 5h, and then decreasing the temperature to 30°C at a rate of 1°C / min). The annealed glass bricks are subjected to XRD test to obtain Figure 1 It is known that it is in a glassy state, and then transferred to a precision annealing furnace for nucleation treatment; the nucleation temperature is 540°C, and the nucleation time is 200 minutes;

[0319] Step 3 is the same as in Example 24;

[0320] Step 4: The process of trimming, cutting into pieces, rough grinding and polishing is the same as that of Example 1. After measurement, the crystallinity is 47 wt %. The obtained part of the crystallized glass original piece is subjected to XRD test and the obtained Figure 2 , it can be seen that it is in a partially crystallized state.

[0321] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 14 in Table 2 (refer to Example 24) to obtain a 3D microcrystalline glass sample 25.

[0322] The above-mentioned 3D microcrystalline glass sample 25 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 25 after hot bending was 87wt%, and the precipitated crystalline phase was lithium disilicate + petalite + β-quartz solid solution, and the average particle size of the crystal was 18nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.39; the light transmittance of the wavelength of 360nm was 88.80%, the average light transmittance of the wavelength of 380-780nm was 92.70%, the average light transmittance of the wavelength of 360-400nm was 89.80%, and the haze was 0.09%.

[0323] Step 6: The 3D glass-ceramics obtained in step 5 is subjected to chemical strengthening treatment by immersing the glass in molten 100wt% NaNO at a temperature of 450°C. 3 After being in the solution for 10 hours, a 3D glass-ceramic product 25 is finally obtained.

[0324] Example 26 Preparation method of 3D microcrystalline glass:

[0325] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 68.73%;Al 2 O 3 4.13%; MgO 0.98%, ZnO1.68%, Na 2 O 0.45%; Li 2 O 20.01%; B 2 O 3 1.49%, nucleating agent (0.81% P 2 O 5 ; 1.72% ZrO 2), and 0.5wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1550°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0326] Step 2 is the same as in Example 25;

[0327] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 615° C. for 120 min to obtain partially crystallized glass bricks;

[0328] Step 4: The process of trimming, cutting into pieces, rough grinding and polishing is the same as that of Example 1. After measurement, the crystallinity is 55 wt %. The obtained part of the crystallized glass original piece is subjected to XRD test and the obtained Figure 3 , it can be seen that it is in a partially crystallized state.

[0329] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 15 in Table 2 (refer to Example 22) to obtain a 3D microcrystalline glass sample 26.

[0330] The above-mentioned 3D microcrystalline glass sample 26 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 26 after hot bending was 91wt%, the precipitated crystal phase was petalite, and the average particle size of the crystal was 23nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.42; the light transmittance of the wavelength of 360nm was 88.13%, the average light transmittance of the wavelength of 380-780nm was 92.80%, the average light transmittance of the wavelength of 360-400nm was 89.90%, and the haze was 0.11%.

[0331] Example 27 Preparation method of 3D microcrystalline glass:

[0332] Step 1: The same as Example 18, except for the temperature of the melt forming process; the temperature of the melt forming process in this embodiment is 1610°C;

[0333] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 460°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 480°C, and the nucleation treatment time is 360min;

[0334] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 550° C. for 300 min to obtain partially crystallized glass bricks;

[0335] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 6wt%.

[0336] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 1 in Table 2 (the same as Example 1) to obtain a 3D microcrystalline glass sample 27.

[0337] The above-mentioned 3D microcrystalline glass sample 27 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test were analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 27 was 14wt%, the precipitated crystalline phase was lithium silicate, and the average particle size of the crystal was 10nm. When the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 27 was 0.15; the light transmittance at a wavelength of 360nm was 90.60%, the average light transmittance at a wavelength of 380-780nm was 93.00%, the average light transmittance at a wavelength of 360-400nm was 91.40%, and the haze was 0.07%.

[0338] Example 28 Preparation method of 3D glass-ceramics:

[0339] Step 1 is the same as in Example 27;

[0340] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 460°C for 5h, decreasing to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 500°C, and the nucleation treatment time is 300min;

[0341] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 570° C. for 280 min to obtain partially crystallized glass bricks;

[0342] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 8wt%.

[0343] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 1 in Table 2 to obtain a 3D microcrystalline glass sample 28.

[0344] The above-mentioned 3D microcrystalline glass sample 28 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test were analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 28 was 16wt%, the precipitated crystalline phase was lithium silicate, and the average particle size of the crystal was 15nm. When the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 28 was 0.25; the light transmittance at a wavelength of 360nm was 90.10%, the average light transmittance at a wavelength of 380-780nm was 92.80%, the average light transmittance at a wavelength of 360-400nm was 91.20%, and the haze was 0.09%.

[0345] Example 29 Preparation method of 3D glass-ceramics:

[0346] Step 1 is the same as in Example 27;

[0347] Step 2 is the same as in Example 28;

[0348] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 560° C. for 240 min to obtain partially crystallized glass bricks;

[0349] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 9wt%.

[0350] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 1 in Table 2 to obtain a 3D microcrystalline glass sample 28.

[0351] The above-mentioned 3D microcrystalline glass sample 29 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 29 was 17wt%, the precipitated crystalline phase was lithium silicate, and the average particle size of the crystal was 13nm. When the light source was limited to D65, the absolute value of the b value of the 3D microcrystalline glass sample 29 was 0.23; the light transmittance at a wavelength of 360nm was 90.50%, the average light transmittance at a wavelength of 380-780nm was 92.70%, the average light transmittance at a wavelength of 360-400nm was 91.50%, and the haze was 0.08%.

[0352] Example 30 Preparation method of 3D microcrystalline glass:

[0353] Step 1 is the same as in Example 17;

[0354] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 500°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 600°C, and the time of the nucleation treatment is 80min;

[0355] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 610° C. for 180 min to obtain partially crystallized glass bricks;

[0356] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 37 wt%.

[0357] Step 5: Perform 3D heat bending on a portion of the crystallized glass original sheet, using the heat bending process No. 3 in Table 2 to obtain a 3D micro-ceramic glass sample 30. Perform XRD test on the obtained portion of the crystallized glass original sheet, and obtain Figure 4 , it can be seen that it is in a partially crystallized state.

[0358] The above-mentioned 3D microcrystalline glass sample 30 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 30 after hot bending was 75wt%, and the precipitated crystal phase was a solid solution of petalite + β-quartz, and the average particle size of the crystal was 18nm. It was determined that when the light source was limited to D65, the absolute value of the b value was 0.35; the light transmittance of a wavelength of 360nm was 88.20%, the average light transmittance of a wavelength of 380-780nm was 92.60%, the average light transmittance of a wavelength of 360-400nm was 90.00%, and the haze was 0.11%.

[0359] Example 31 Preparation method of 3D glass-ceramics:

[0360] Step 1 is the same as in Example 2;

[0361] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 600°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 800°C, and the time of the nucleation treatment is 30min;

[0362] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 870° C. for 15 minutes to obtain partially crystallized glass bricks;

[0363] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 88wt%.

[0364] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 4 in Table 2 to obtain a 3D microcrystalline glass sample 31.

[0365] The above-mentioned 3D microcrystalline glass sample 31 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 31 after hot bending was 99wt%, the precipitated crystal phase was β-spodumene, and the average particle size of the crystal was 48nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 2.60; the light transmittance of the wavelength of 360nm was 74.10%, the average light transmittance of the wavelength of 380-780nm was 89.30%, the average light transmittance of the wavelength of 360-400nm was 80.50%, and the haze was 0.78%.

[0366] Example 32 Preparation method of 3D microcrystalline glass:

[0367] Step 1 is the same as in Example 2;

[0368] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 600°C for 5h, and then reduce the temperature to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 780°C, and the time of the nucleation treatment is 60min;

[0369] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 900° C. for 5 minutes to obtain partially crystallized glass bricks;

[0370] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 58 wt%.

[0371] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 7 in Table 2 to obtain a 3D microcrystalline glass sample 32.

[0372] The above-mentioned 3D microcrystalline glass sample 32 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 32 after hot bending was 98wt%, the precipitated crystal phase was β-spodumene, and the average particle size of the crystal was 81nm. It was determined that when the light source was limited to D65, the absolute value of the b value was 2.80; the light transmittance of the wavelength of 360nm was 62.00%, the average light transmittance of the wavelength of 380-780nm was 88.60%, the average light transmittance of the wavelength of 360-400nm was 65.80%, and the haze was 0.72%.

[0373] Example 33 Preparation method of 3D microcrystalline glass:

[0374] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 67.45%;Al 2 O 3 14.20%; CaO 0.50%; MgO 1.79%; Na 2 O 1.56%; Li 2 O

[0375] 9.70%; nucleating agent (2.18% P 2 O 5 ; 0.81% TiO 2 ; 1.31% ZrO 2 ; 0.5% Y 2 O 3 ), and 0.8wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1713.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1650°C, the melting time is 5h, and the glass bricks are poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0376] Step 2: After cooling the glass brick obtained in step 1 to 800°C, transfer it to an annealing furnace for annealing (annealing process is 500°C for 5h, and then reduce the temperature to 30°C at 1°C / min), and then transfer it to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 650°C, and the time of the nucleation treatment is 160min;

[0377] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 820° C. for 30 minutes to obtain partially crystallized glass bricks;

[0378] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 90wt%.

[0379] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 6 in Table 2 to obtain a 3D microcrystalline glass sample 33.

[0380] The above-mentioned 3D microcrystalline glass sample 33 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 33 after hot bending was 100wt%, the precipitated crystal phase was β-spodumene, and the average particle size of the crystal was 98nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 3.8; the light transmittance of the wavelength of 360nm was 63.10%, the average light transmittance of the wavelength of 380-780nm was 88.20%, the average light transmittance of the wavelength of 360-400nm was 65.40%, and the haze was 0.98%.

[0381] Example 34 Preparation method of 3D microcrystalline glass:

[0382] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 66.65%;Al 2 O 3 10.87%; MgO 2.44%; ZnO 2.82%; Na 2 O 0.21%; K 2 O 0.21%; Li 2 O 9.88%; B 2 O 3 0.94%; nucleating agent (1.85% P 2 O 5 ; 2.00% ZrO 2 ; 2.13%

[0383] CaF 2 ), and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1640°C, the melting time is 4h, and the glass bricks are poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0384] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 500°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the nucleation treatment temperature is 620°C, and the nucleation treatment time is 240min;

[0385] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 650° C. for 40 minutes to obtain partially crystallized glass bricks;

[0386] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 68wt%.

[0387] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 7 in Table 2 to obtain a 3D microcrystalline glass sample 34.

[0388] The above-mentioned 3D microcrystalline glass sample 34 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 34 after hot bending was 79wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 65nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.76; the light transmittance of the wavelength of 360nm was 84.22%, the average light transmittance of the wavelength of 380-780nm was 91.00%, the average light transmittance of the wavelength of 360-400nm was 87.50%, and the haze was 0.16%.

[0389] Example 35 Preparation method of 3D microcrystalline glass:

[0390] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 64.55%;Al 2 O 3 10.45%; MgO 2.37%; ZnO 2.73%; Na 2 O 0.21%; K 2 O 0.20%; Li 2 O 9.58%; B 2 O 3 0.91%; nucleating agent (1.94% P 2 O 5 ; 2.91% TiO 2 ; 2.02% ZrO 2 ; 2.13% CaF 2), and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1640°C, the melting time is 4h, and the glass bricks are poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0391] Step 2 and step 3 are the same as in Example 35;

[0392] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 82 wt%.

[0393] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 6 in Table 2 to obtain a 3D microcrystalline glass sample 35.

[0394] The above-mentioned 3D microcrystalline glass sample 35 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 35 after hot bending was 86wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 42nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.68; the light transmittance of the wavelength of 360nm was 85.42%, the average light transmittance of the wavelength of 380-780nm was 91.10%, the average light transmittance of the wavelength of 360-400nm was 87.20%, and the haze was 0.19%.

[0395] Example 36 Preparation method of 3D microcrystalline glass:

[0396] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 70.13%;Al 2 O 3 11.50%; MgO 2.57%; ZnO 2.97%; Na 2 O 0.22%; K 2 O 0.22%; Li 2 O 10.40%; B 2 O 3 0.99%; Nucleating agent (0.84% ​​P 2 O 5 ; 0.16% CaF 2), and 0.7wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1711.9g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1640°C, the melting time is 3h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel.

[0397] Step 2 and step 3 are the same as in Example 34;

[0398] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 63wt%.

[0399] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 5 in Table 2 to obtain a 3D microcrystalline glass sample 36.

[0400] The above-mentioned 3D microcrystalline glass sample 36 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 36 after hot bending was 70wt%, the precipitated crystal phase was β-quartz solid solution, and the average particle size of the crystal was 37nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.53; the light transmittance of the wavelength of 360nm was 86.00%, the average light transmittance of the wavelength of 380-780nm was 92.20%, the average light transmittance of the wavelength of 360-400nm was 88.60%, and the haze was 0.10%.

[0401] Example 37 Preparation method of 3D microcrystalline glass:

[0402] Step 1: Same as Example 17, the only difference is the temperature and melting time of the melting molding process. The temperature of the melting molding process in this example is 1650°C and the melting time is 2h;

[0403] Step 2: After the glass brick obtained in step 1 is cooled to 800°C, it is transferred to an annealing furnace for annealing (annealing process is 500°C for 5h, and then reduced to 30°C at 1°C / min), and then transferred to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 600°C, and the time of the nucleation treatment is 80min;

[0404] Step 3: After nucleation, the glass bricks are further subjected to crystallization treatment in a precision annealing furnace at a temperature of 600° C. for 240 minutes to obtain partially crystallized glass bricks;

[0405] Step 4: The process of trimming, cutting into slices, rough grinding and polishing is the same as that in Example 1. After measurement, the crystallinity is 75wt%.

[0406] Step 5: Perform 3D heat bending on part of the crystallized glass original sheet, using the heat bending process numbered 6 in Table 2 to obtain a 3D microcrystalline glass sample 37.

[0407] The above-mentioned 3D microcrystalline glass sample 37 was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 37 after hot bending was 88wt%, the precipitated crystal phase was a solid solution of petalite + β-quartz, and the average particle size of the crystal was 57nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.38; the light transmittance of the wavelength of 360nm was 88.40%, the average light transmittance of the wavelength of 380-780nm was 92.80%, the average light transmittance of the wavelength of 360-400nm was 90.10%, and the haze was 0.12%.

[0408] Example 38 Preparation method of 3D microcrystalline glass:

[0409] Step 1, step 2, step 3 and step 4 are the same as those in Example 22;

[0410] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process numbered 20 in Table 2; the hot bending process includes 3 preheating stations, 4 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 450°C, the temperature of the second preheating station is 600°C, and the temperature of the third preheating station is 650°C. The temperature of the first hot pressing station is 760°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 750°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 720°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the fourth hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, the hot pressing station and the cooling station is the same, which is 140 seconds, and a 3D microcrystalline glass sample 22F is obtained.

[0411] The above-mentioned 3D microcrystalline glass sample 22F was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 22F after hot bending was 84wt%, the precipitated crystalline phase was petalite + lithium disilicate, and the average particle size of the crystal was 18nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.43; the light transmittance of the wavelength of 360nm was 88.15%, the average light transmittance of the wavelength of 380-780nm was 92.77%, the average light transmittance of the wavelength of 360-400nm was 89.45%, and the haze was 0.11%.

[0412] Example 39 Preparation method of 3D microcrystalline glass:

[0413] Step 1, step 2, step 3 and step 4 are the same as those in Example 22;

[0414] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process numbered 21 in Table 2; the hot bending process includes 5 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 430°C, the temperature of the second preheating station is 500°C, the temperature of the third preheating station is 600°C, the temperature of the fourth preheating station is 680°C, and the temperature of the fifth preheating station is 720°C. The temperature of the first hot pressing station is 745°C, the upper pressure is 0.5MPa, and the lower pressure is 0.5MPa; the temperature of the second hot pressing station is 760°C, the upper pressure is 0MPa, and the lower pressure is 0MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, the hot pressing station and the cooling station is the same, which is 140 seconds, and a 3D microcrystalline glass sample 22G is obtained.

[0415] The above-mentioned 3D microcrystalline glass sample 22G was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test was analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 22G after hot bending was 90wt%, the precipitated crystalline phase was petalite + lithium disilicate, and the average particle size of the crystal was 22nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 0.55; the light transmittance of the wavelength of 360nm was 86.12%, the average light transmittance of the wavelength of 380-780nm was 92.40%, the average light transmittance of the wavelength of 360-400nm was 88.40%, and the haze was 0.10%.

[0416] Comparative Example

[0417] Comparative Example 1 Preparation method of 3D glass-ceramics:

[0418] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 62.40%;Al 2 O 3 13.24%; MgO 4.46%; Na 2 O 1.46%; Li 2 O 9.04%, nucleating agent (0.94% P 2 O 5 ; 6.58% ZrO 2 ; 1.88% TiO 2 A total of 9.40% of nucleating agent), and 0.8wt% of NaCl accounting for the total weight of the nucleating agent and the preparation raw materials, the total weight of the above raw materials is 1713.6g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0419] Step 2 is the same as Example 4; it can be seen that the nucleated glass original sheet has precipitated crystals and is in a ceramic state, which does not meet the conditions for the subsequent hot bending process.

[0420] Comparative Example 2 Preparation method of 3D glass-ceramics:

[0421] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 60.70%;Al 2 O 3 12.87%; MgO 4.34%; Na 2 O 1.42%; Li 2 O 8.79%, nucleating agent (0.91% P 2 O 5 ; 9.14% ZrO 2 ; 1.83% TiO 2 A total of 11.88% of nucleating agent), and 0.8wt% of NaCl accounting for the total weight of the nucleating agent and the preparation raw materials, the total weight of the above raw materials is 1713.6g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1630°C, the melting time is 5h, and poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick;

[0422] Step 2: When the glass brick obtained in step 1 is cooled to 800°C, crystals precipitate in the center, causing stress difference inside the glass brick, causing the glass brick to break and become unable to be machined.

[0423] Comparative Example 3 Preparation method of 3D glass-ceramics:

[0424] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 67.45%;Al 2 O 3 14.20%; CaO 0.50%; MgO 1.79%; Na 2 O 1.56%; Li 2 O

[0425] 9.70%; nucleating agent (2.18% P 2 O 5 ; 1.31% ZrO 2 ; 0.81% TiO 2 and 0.5% Y 2 O 3 ), and 0.8wt% of the total weight of the nucleating agent and the raw materials for preparation, the total weight of the above raw materials is 1708.5g, and the raw materials are fully mixed and melted in a high-temperature lifting furnace. The temperature of the melting and molding treatment is 1630°C, the melting time is 5h, and the glass bricks are cast into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0426] Step 2 is the same as in Example 4;

[0427] Step 3: After nucleation, the glass bricks continue to undergo crystallization treatment in a precision annealing furnace. The crystallization temperature is 930°C and the crystallization time is 30 minutes. After the crystallization treatment, the glass bricks undergo uncontrollable crystallization due to the excessively high crystallization temperature, and stress differences occur inside the glass bricks, causing the glass bricks to break and become unable to be machined.

[0428] Comparative Example 4 Preparation method of 3D glass-ceramics:

[0429] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 70.33%;Al 2 O 3 14.82%; Na 2 O 1.63%; Li 2 O 10.11%; MgO 1.34%; ZnO

[0430] 1.04%, nucleating agent (0.52% P 2 O 5 ; 0.21% ZrO 2 ), and clarifiers NaCl and SnO accounting for 0.4wt% and 0.4wt% of the total mass of the nucleating agent and the raw materials, respectively.2 The total weight of the above raw materials is 1708.5g. After being fully mixed, they are melted and formed in a high-temperature lifting furnace. The temperature of the melting and forming treatment is 1630°C and the melting time is 5h. The raw materials are poured into a mold made of ASTM SA213 / TP310S austenitic chromium-nickel stainless steel to obtain a glass brick.

[0431] The conditions of step 2 and step 3 are the same as those of Example 33. XRD test is performed on the glass bricks after nucleation treatment. It can be seen that due to too little nucleating agent, no crystal nuclei are formed, uncontrollable crystallization occurs during the crystallization treatment, and stress difference occurs inside the glass, causing the hot-bent glass to break.

[0432] Comparative Example 5 Preparation method of 3D glass-ceramics:

[0433] Step 1: Prepare and weigh the raw materials for glass preparation (containing the following components in molar percentage: SiO 2 70.45%;Al 2 O 3 13.16%; MgO 2.78%; Na 2 O 0.56%; Li 2 O 7.98%; B 2 O 3

[0434] 1.00%; Nucleating agent (1.67% P 2 O 5 ; 1.30% ZrO 2 ; 0.60%TiO 2 and 0.5% Y 2 O 3 ), and 0.4wt% and 0.3wt% of the total mass of the nucleating agent and the raw materials for preparation of the clarifier NaCl and CeO 2 The total weight of the above raw materials is 1711.9g. After being fully mixed, they are melted and formed in a high-temperature lifting furnace. The temperature of the melting and forming treatment is 1630°C, the melting time is 5h, and they are poured into a mold made of ASTMSA213 / TP310S austenitic chromium-nickel stainless steel to obtain glass bricks;

[0435] Step 2: After cooling the glass bricks obtained in step 1 to 900°C, transfer them to a precision annealing furnace for nucleation treatment; the temperature of the nucleation treatment is 850°C, and the time of the nucleation treatment is 120 minutes; after the nucleation treatment, the glass bricks experience uncontrollable crystallization due to the excessively high nucleation temperature, and stress differences occur inside the glass bricks, causing the glass bricks to break, making subsequent processing impossible.

[0436] Comparative Example 6 Preparation method of 3D glass-ceramics:

[0437] Step 1, step 2, step 3 and step 4 are the same as those in Example 22;

[0438] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process numbered 16 in Table 2; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 480°C, the temperature of the second preheating station is 600°C, the temperature of the third preheating station is 650°C, and the temperature of the fourth preheating station is 720°C. The temperature of the first hot pressing station is 940°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 920°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s. The 3D glass-ceramic sample 22B was obtained.

[0439] The above-mentioned 3D microcrystalline glass sample 22B was tested using a X-ray diffractometer. The instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test were analyzed. Among them, the crystallinity of the 3D microcrystalline glass sample 22B after hot bending was 100wt%, the precipitated crystal phase was β-spodumene + lithium disilicate, and the average particle size of the crystal was 111nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 7.45; the light transmittance of a wavelength of 360nm was 64.10%, the average light transmittance of a wavelength of 380-780nm was 86.50%, the average light transmittance of a wavelength of 360-400nm was 69.20%, and the haze was 0.99%. Due to the excessively high temperature of the hot pressing, the microcrystalline glass finally prepared had an excessively high average crystal particle size, which resulted in an increase in the b value and a decrease in the light transmittance. When the b value was too high, the microcrystalline glass was blue, which affected the imaging.

[0440] Comparative Example 7 Preparation method of 3D glass-ceramics:

[0441] Step 1, step 2, step 3 and step 4 are the same as those in Example 22;

[0442] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process No. 17 in Table 2; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 450℃, the temperature of the second preheating station is 600℃, the temperature of the third preheating station is 650℃, and the temperature of the fourth preheating station is 720℃. The temperature of the first hot pressing station is 930℃, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 920℃, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 600℃, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450℃, and the temperature of the second cooling station is 300℃. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s. The 3D glass-ceramic sample 22C was obtained.

[0443] The above-mentioned 3D microcrystalline glass sample 22C was tested using a X-ray diffractometer, and the instrument setting conditions were the same as those in Example 1. The X-ray diffraction data after the test were analyzed, wherein the crystallinity of the 3D microcrystalline glass sample 22C after hot bending was 100wt%, the precipitated crystal phase was β-spodumene + lithium disilicate, and the average particle size of the crystal was 124nm. It was measured that when the light source was limited to D65, the absolute value of the b value was 7.86; the light transmittance of a wavelength of 360nm was 62.40%, the average light transmittance of a wavelength of 380-780nm was 87.30%, the average light transmittance of a wavelength of 360-400nm was 68.20%, and the haze was 1.10%. Due to the excessively high temperature of the hot pressing, the microcrystalline glass finally prepared had an excessively high average crystal particle size, which resulted in an increase in the b value and a decrease in the light transmittance. When the b value was too high, the microcrystalline glass was bluish, affecting the imaging.

[0444] Comparative Example 8 Preparation method of 3D glass-ceramics:

[0445] Step 1, step 2, step 3 and step 4 are the same as those in Example 22;

[0446] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process numbered 18 in Table 2; the hot bending process includes 4 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 450°C, the temperature of the second preheating station is 500°C, the temperature of the third preheating station is 650°C, and the temperature of the fourth preheating station is 650°C. The temperature of the first hot pressing station is 580°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 600°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 600°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s. A 3D glass-ceramic sample 22D is obtained. Since the hot pressing temperature is too low, the 3D glass-ceramic sample 22D cannot be hot-bent into a target shape.

[0447] Comparative Example 9 Preparation method of 3D glass-ceramics:

[0448] Step 1, step 2, step 3 and step 4 are the same as those in Example 22;

[0449] Step 5: Part of the crystallized glass original sheet is subjected to 3D hot bending treatment. The hot bending process adopts the hot bending process No. 19 in Table 2; the hot bending treatment includes 3 preheating stations, 3 hot pressing stations and 2 cooling stations. The temperature of the first preheating station is 500°C, the temperature of the second preheating station is 550°C, and the temperature of the third preheating station is 600°C. The temperature of the first hot pressing station is 600°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the second hot pressing station is 580°C, the upper pressure is 0.1MPa, and the lower pressure is 0.1MPa; the temperature of the third hot pressing station is 550°C, the upper pressure is 0MPa, and the lower pressure is 0MPa. The temperature of the first cooling station is 450°C, and the temperature of the second cooling station is 300°C. Among them, the working time of each station in the preheating station, hot pressing station and cooling station is the same, which is 90s, and a 3D microcrystalline glass sample 22E is obtained. Since the hot pressing temperature is too low, the 3D glass-ceramic sample 22E cannot be hot-bent into the target shape.

[0450] Application Examples

[0451] The mechanical parameters of the 3D microcrystalline glass obtained after chemical strengthening of the above-mentioned Example 1, Example 2, Example 4, Example 7, Example 12, Example 16, Example 22, Example 23, Example 24 and Example 25 were measured. The thickness of the tested glass was 0.65 mm. The test results are shown in Table 3.

[0452] The SLP-2000 stress meter was used for testing, with the photoelastic coefficient set to 25.5 and the refractive index set to 1.54. This is a routine test. The test results include surface compressive stress, compressive stress depth and average tensile stress. The tensile stress line density is a calculated value. The sum of the tensile stress tested by the SLP-2000 stress meter is divided by the glass thickness.

[0453] Surface compressive stress (MPa): After chemical strengthening of glass, the alkali metal ions with smaller radius on the surface are replaced by alkali metal ions with larger radius. Due to the crowding effect of the alkali metal ions with larger radius, compressive stress is generated on the glass surface, which is called surface compressive stress.

[0454] Compressive stress depth (μm): the distance from the surface of chemically strengthened glass to the position where the compressive stress is zero;

[0455] Average tensile stress CT-AV (MPa): the ratio of the sum of tensile stress obtained by SLP-2000 stress meter test to the thickness of tensile stress area;

[0456] Tensile stress line density CT-LD: obtained by SLP-2000 stress meter test, the ratio of the tensile stress integral of chemically strengthened glass to the glass thickness at its thickness section;

[0457] Whole machine drop test: A method for testing the strength of tempered glass. A tempered glass sheet is attached to a mobile phone or other electronic device sample, and then dropped from a height to record the height at which the glass breaks. This height value can reflect the strength of the glass. This test method is called a whole machine drop test. This patented test method is to drop a mobile phone with a tempered glass sheet and a weight of 180g onto 120-grit sandpaper, which is tightly attached to a marble bottom plate.

[0458] Vickers hardness (Hv) (300N pressure maintained for 10s): Use a diamond right pyramid indenter with an angle of 136 degrees between relative surfaces to press into the surface of the test sample under a load of 300N. After holding for 10s, remove the load and measure the diagonal length d of the indentation. Then calculate the surface area of ​​the indentation. Finally, find the average pressure on the indentation surface area, which is the Vickers hardness value of the glass, represented by the symbol HV.

[0459] Table 3 Mechanical parameters determination

[0460]

[0461]

[0462] It can be seen from the above table that the surface compressive stress of the 3D microcrystalline glass product after chemical strengthening in the embodiment is 108-514MPa, the compressive stress depth is 109-121μm, the average tensile stress CT-AV is 42-93MPa, the tensile stress line density CT-LD is 30145-43157, the drop test height of the whole machine is 1.51-1.82m, and the Vickers hardness (300N pressure maintained for 10s) of the 3D microcrystalline glass product after chemical strengthening is 712-741Hv.

[0463] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.

Claims

1. An electronic terminal, characterized in that: The electronic terminal includes a 3D microcrystalline glass finished product, and the 3D microcrystalline glass finished product includes 3D microcrystalline glass; the crystallinity of the 3D microcrystalline glass is 14wt%-100wt%; the average particle size of the crystals of the 3D microcrystalline glass is 10-100nm; the absolute value of the b value of the 3D microcrystalline glass is 0.1-3.

5.

2. The electronic terminal according to claim 1, characterized in that: The crystallinity of the 3D glass-ceramics is 14-30wt%, or the crystallinity of the 3D glass-ceramics is 50-100wt%; or the crystallinity of the 3D glass-ceramics is 31-49wt%; And / or, the average particle size of the crystals of the 3D glass-ceramics is 10nm-57nm, preferably 15-30nm; And / or, the thickness of the 3D glass-ceramics is 0.02-5 mm. Preferably, the thickness of the 3D glass-ceramics is 0.35-1.2 mm.

3. The electronic terminal according to claim 1 or 2, characterized in that: The average transmittance of the 3D glass-ceramics for light with a wavelength of 380-780 nm is 88%-93%, preferably 90%-93%; And / or, the average transmittance of the 3D glass-ceramics at a wavelength of 360-400 nm is 65-91.5%, preferably 79-91%, and more preferably 85-91%; and / or, The transmittance of the 3D glass-ceramics at a wavelength of 360 nm is greater than or equal to 80%, preferably greater than or equal to 85%, and more preferably greater than or equal to 86%.

4. The electronic terminal according to any one of claims 1 to 3, characterized in that: The absolute value of the b value of the 3D glass-ceramics is 0.3-1.5, preferably 0.3-1.0; And / or, the haze of the 3D glass-ceramics is 0.07-1.0%, preferably 0.07-0.5%.

5. The electronic terminal according to any one of claims 1 to 4, characterized in that: The crystalline phase of the 3D microcrystalline glass is one or more of lithium silicate, lithium disilicate, β-quartz, β-quartz solid solution, petalite, β-spodumene, β-spodumene solid solution, nepheline, cordierite, mullite, apatite, zirconium dioxide, zinc spinel, magnesium aluminum spinel and rutile.

6. The electronic terminal according to any one of claims 1 to 5, characterized in that: The 3D glass-ceramics contains the following proportions of oxides in mol%:

7. The electronic terminal according to any one of claims 1 to 6, characterized in that: The 3D glass-ceramics contains the following proportions of oxides in mol%: 65.1% to 71.8% SiO2, preferably 68% to 71.8% SiO2, more preferably 68% to 69.5% SiO2; and / or, 3% to 8.51% Al2O3, preferably 3% to 5.5% Al2O3, more preferably 3% to 5.3% Al2O3; and / or, 0% to 1.6% B2O3, preferably 0% to 1.5% B2O3; and / or, 0% to 1.4% MgO; and / or, 18.8% to 25% Li2O, preferably 20.01% to 25% Li2O, more preferably 20.5% to 25% Li2O.

8. The electronic terminal according to any one of claims 1 to 7, characterized in that: The 3D glass-ceramics includes a nucleating agent, and the amount of the nucleating agent is 1-9 mol% of the total amount of the nucleating agent and the glass-ceramics oxide. Preferably, in the 3D glass-ceramics, the amount of the nucleating agent is 2 mol%-5 mol%.

9. The electronic terminal according to any one of claims 6 to 8, characterized in that: The rare earth oxide is selected from La2O3, Eu2O3, Pr6O 11 , one or more of Nd2O3, Er2O3 and Dy2O3.

10. The electronic terminal according to any one of claims 1 to 9, characterized in that: The 3D glass-ceramics contains SiO2 and Al2O3 in a total amount greater than 60% by mol%, preferably 68-80%; And / or, the content of Na2O+Li2O is 7%-30% by mol%, preferably 10% to 26%.

11. The electronic terminal according to any one of claims 8 to 10, characterized in that: Calculated as oxide, fluoride or single substance, the nucleating agent includes one or more of P2O5, TiO2, ZrO2, Cr2O3, CaF2, LiF, NaF, KF, Y2O3, Au, Ag and Cu; preferably one or more of P2O5, TiO2 and ZrO2.

12. The electronic terminal according to any one of claims 1 to 11, characterized in that: The 3D microcrystalline glass includes a clarifier, which includes one or more of NaCl, Na2SO4, SnO2, As2O3, Sb2O3, NaNO3, KNO3, CeO2 and (NH4)2SO4; preferably one or more of NaCl, SnO2, NaNO3 and CeO2.

13. The electronic terminal according to any one of claims 1 to 12, characterized in that: The crystallized glass raw material of the 3D glass-ceramics is glass having a crystallinity of 5wt%-90wt% after nucleation and crystallization treatment, preferably glass having a crystallinity of 30wt%-90wt%; and / or, The crystallized glass raw material of the 3D microcrystalline glass is glass with crystals having an average particle size of 5nm-50nm after nucleation and crystallization treatment.

14. The electronic terminal according to any one of claims 1 to 13, characterized in that: The 3D glass-ceramics finished product is obtained by subjecting 3D glass-ceramics to chemical strengthening treatment, and preferably, the drop height of the 3D glass-ceramics after chemical strengthening is greater than 1.5 m.

15. The electronic terminal according to any one of claims 1 to 14, characterized in that: The 3D glass-ceramics is flat or curved; and / or, the 3D glass-ceramics is transparent or opaque.

16. The electronic terminal according to any one of claims 1 to 15, characterized in that: The electronic terminal is one of a mobile phone display screen, a tablet computer display screen, a handheld game console, a portable digital device, a vehicle-mounted central control screen, an electronic whiteboard glass, and a smart home touch screen.

17. A 3D glass-ceramic, characterized in that: The crystallinity of the 3D microcrystalline glass is 14wt%-100wt%; the average particle size of the crystals of the 3D microcrystalline glass is 10-100nm; and the absolute value of the b value of the 3D microcrystalline glass is 0.1-3.

5.

18. The electronic terminal according to claim 17, characterized in that: The crystallinity of the 3D glass-ceramics is 14-30wt%, or the crystallinity of the 3D glass-ceramics is 50-100wt%; or the crystallinity of the 3D glass-ceramics is 31-49wt%; And / or, the average particle size of the crystals of the 3D glass-ceramics is 10nm-57nm, preferably 15-30nm; And / or, the thickness of the 3D glass-ceramics is 0.02-5 mm. Preferably, the thickness of the 3D glass-ceramics is 0.35-1.2 mm.

19. The electronic terminal according to claim 17 or 18, characterized in that: The average transmittance of the 3D glass-ceramics for light with a wavelength of 380-780 nm is 88%-93%, preferably 90%-93%; And / or, the average transmittance of the 3D glass-ceramics at a wavelength of 360-400 nm is 65-91.5%, preferably 79-91%, and more preferably 85-91%; and / or, The transmittance of the 3D glass-ceramics at a wavelength of 360 nm is greater than or equal to 80%, preferably greater than or equal to 85%, and more preferably greater than or equal to 86%.

20. The electronic terminal according to any one of claims 17 to 19, characterized in that: The absolute value of the b value of the 3D glass-ceramics is 0.3-1.5, preferably 0.3-1.0; And / or, the haze of the 3D glass-ceramics is 0.07-1.0%, preferably 0.07-0.5%.

21. The electronic terminal according to any one of claims 17 to 20, characterized in that: The crystalline phase of the 3D microcrystalline glass is one or more of lithium silicate, lithium disilicate, β-quartz, β-quartz solid solution, petalite, β-spodumene, β-spodumene solid solution, nepheline, cordierite, mullite, apatite, zirconium dioxide, zinc spinel, magnesium aluminum spinel and rutile.

22. The electronic terminal according to any one of claims 17 to 21, characterized in that: The 3D glass-ceramics contains the following proportions of oxides in mol%:

23. The electronic terminal according to any one of claims 17 to 22, characterized in that: The 3D glass-ceramics contains the following proportions of oxides in mol%: 65.1% to 71.8% SiO2, preferably 68% to 71.8% SiO2, more preferably 68% to 69.5% SiO2; and / or, 3% to 8.51% Al2O3, preferably 3% to 5.5% Al2O3, more preferably 3% to 5.3% Al2O3; and / or, 0% to 1.6% B2O3, preferably 0% to 1.5% B2O3; and / or, 0% to 1.4% MgO; and / or, 18.8% to 25% Li2O, preferably 20.01% to 25% Li2O, more preferably 20.5% to 25% Li2O.

24. The electronic terminal according to any one of claims 17 to 23, characterized in that: The 3D glass-ceramics includes a nucleating agent, and the amount of the nucleating agent is 1-9 mol% of the total amount of the nucleating agent and the glass-ceramics oxide. Preferably, in the 3D glass-ceramics, the amount of the nucleating agent is 2 mol%-5 mol%.

25. The electronic terminal according to any one of claims 21 to 24, characterized in that: The rare earth oxide is selected from LaO3, Eu2O3, Pr6O 11 , one or more of Nd2O3, Er2O3 and Dy2O3.

26. The electronic terminal according to any one of claims 17 to 25, characterized in that: The 3D glass-ceramics contains SiO2 and Al2O3 in a total amount greater than 60% by mol%, preferably 68-80%; And / or, the content of Na2O+Li2O is 7%-30% by mol%, preferably 10% to 26%.

27. The electronic terminal according to any one of claims 17 to 26, characterized in that: Calculated as oxide, fluoride or single substance, the nucleating agent includes one or more of P2O5, TiO2, ZrO2, Cr2O3, CaF2, LiF, NaF, KF, Y2O3, Au, Ag and Cu; preferably one or more of P2O5, TiO2 and ZrO2.

28. The electronic terminal according to any one of claims 17 to 27, characterized in that: The 3D microcrystalline glass includes a clarifier, which includes one or more of NaCl, Na2SO4, SnO2, As2O3, Sb2O3, NaNO3, KNO3, CeO2 and (NH4)2SO4; preferably one or more of NaCl, SnO2, NaNO3 and CeO2.

29. The electronic terminal according to any one of claims 17 to 28, characterized in that: The crystallized glass raw material of the 3D microcrystalline glass is glass having a crystallinity of 5wt% to 90wt% after nucleation and crystallization treatment, preferably glass having a crystallinity of 30wt% to 90wt%; and / or, The crystallized glass raw material of the 3D microcrystalline glass is glass with an average particle size of 5nm to 50nm after nucleation and crystallization treatment.

30. The electronic terminal according to claims 17-29, characterized in that: The 3D glass-ceramics finished product is obtained by subjecting 3D glass-ceramics to chemical strengthening treatment, and preferably, the drop height of the 3D glass-ceramics after chemical strengthening is greater than 1.5 m.

31. The electronic terminal according to any one of claims 17 to 30, characterized in that: The 3D glass-ceramics is flat or curved; and / or, the 3D glass-ceramics is transparent or opaque.

32. A 3D glass-ceramic product, characterized in that: The 3D microcrystalline glass finished product is obtained by subjecting the 3D microcrystalline glass described in any one of claims 17 to 31 to chemical strengthening treatment. Preferably, the drop height of the 3D microcrystalline glass after chemical strengthening is greater than 1.5 m.

33. Use of the 3D glass-ceramics described in any one of claims 17 to 31 or the 3D glass-ceramics finished product described in claim 31 in electronic terminals, vehicle windshields, aircraft windshields or aircraft windshields.

34. The method for preparing 3D glass-ceramics according to any one of claims 17 to 31, wherein: The preparation method comprises the following steps: Step 1: Mix the raw materials for preparing 3D glass-ceramics, melt them, cool them, and perform annealing to obtain a glass substrate; Step 2: performing a nucleation treatment on the glass substrate obtained in step 1; wherein the glass substrate may be cut as required before or after the nucleation treatment; Step 3: crystallizing the glass substrate after nucleation in step 2; Step 4: Cutting the crystallized glass substrate as needed to obtain crystallized glass raw material; Step 5: The crystallized glass raw material is subjected to 3D heat bending treatment to obtain a 3D micro-ceramic glass sample; The 3D hot bending process in step 5 is also accompanied by a crystallization process.

35. The method of claim 34, wherein: In the step 1, the melting temperature is 1350-1700°C; preferably, the melting temperature is 1400-1650°C; more preferably, the temperature is cooled to 500-1000°C after melting; further preferably, the method may also include the step of chemically strengthening the 3D glass-ceramic sample to obtain a 3D glass-ceramic finished product.

36. The method according to claim 34 or 35, wherein: In the step 1, the melting time is 1-5 hours; preferably, in the step 3, the crystallization treatment is performed after keeping at 500-900°C for 5-300 minutes; further preferably, in the step 3, one or more of trimming, CNC machine tool processing, rough grinding and / or polishing treatments are also included to obtain the crystallized glass raw material.

37. The method according to any one of claims 34 to 36, wherein: The amount of the nucleating agent added in step 1 is 1-9 mol % of the total amount of the nucleating agent and the glass-ceramic oxide, and the more preferred amount of the nucleating agent is 2-5 mol %.

38. The method according to any one of claims 34 to 37, wherein: The amount of the clarifier added in step 1 is 0-4 wt %, preferably 0.1-2 wt %, of the total mass of the nucleating agent and the glass-ceramic oxide.

39. The method according to any one of claims 34 to 38, wherein: In the step 2, the temperature of the nucleation treatment is 450-800° C., and the time of the nucleation treatment is 30-360 min; further preferably, the temperature of the nucleation treatment is 520-570° C., and the time of the nucleation treatment is 120-300 min.

40. The method according to any one of claims 34 to 39, wherein: In step 3, the temperature of the crystallization treatment is 550-900° C., and the time of the crystallization treatment is 5-300 min; Preferably, the crystallization temperature is 600-850°C, and the crystallization time is 10-240 minutes. More preferably, the temperature of the crystallization treatment is 600-750° C., and the time of the crystallization treatment is 10-150 min.

41. The method according to any one of claims 34 to 40, wherein: The hot bending process in step 5 includes a preheating station, a hot pressing station and a cooling station.

42. The method according to claim 41, wherein: The number of the preheating stations is 1-30, preferably 2-4; the number of the hot pressing stations is 1-30, preferably 1-3; the number of the cooling stations is 1-30, preferably 2-4.

43. The method according to claim 41 or 42, wherein: The temperature of the preheating station is 300-850°C; the temperature of the hot pressing station is 600-920°C and the pressure is 0-6MPa; the temperature of the cooling station is 200-650°C.

44. The method according to any one of claims 41 to 43, wherein: The working time of the preheating station is 20-800 seconds; the working time of the hot pressing station is 20-800 seconds, and the working time of the cooling station is 20-800 seconds; Preferably, the working time of the preheating station is 60-600 seconds; the working time of the hot pressing station is 60-480 seconds, and the working time of the cooling station is 60-600 seconds.